A comparative analysis of a-C:H by infrared spectroscopy and mass selected thermal effusion - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Applied Physics, 1998)
A comparative analysis of quantitative infrared absorption spectra and mass selected thermal effusion transients measured for a large number of hydrogenated amorphous carbon (a-C:H) films is presented in order to establish reliable IR absorption cross sections for the different hydrogen bonding configurations in the material. The structural character of the material and the hydrogen concentration were varied over a wide range from soft and wide band gap polymerlike a-C:H, via so-called diamondlike carbon, to the tetrahedral form of a-C:H deposited from a plasma beam source. The results show that the IR absorption cross sections from molecular hydrocarbons can well be transferred to the solid state as long as the material is of polymeric character, but that this procedure fails as soon as the material converts into a three-dimensional cross-linked and mechanically hard structure. For the latter material an empirical average IR absorption cross section for the C-H stretch band can nevertheless be determined from a comparison between hydrogen effusion and IR spectra. © 1998 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.1998.nat.dphy.IAP.exphys.acompa

Analysis of Random telegraph noise in large-area amorphous double-barrier structures - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review B, 1993)
We have measured the temporal behavior of the perpendicular current through large-area (0.25 mm2) double-barrier structures fabricated from n+-type a-Si:H and quasistoichiometric a-SiNx:H. The current switches randomly between distinct values with an amplitude between 0.5% and 10% of the total current. This behavior is reminiscent of random telegraph noise (RTN) observed in small-area (<1 μm2) devices. The power spectra of the RTN can be fitted by a superposition of Lorentzians from which effective switching rates can be deduced. They are thermally activated and exhibit a dependence on the voltage applied to the sample. The RTN switching can be influenced optically by illuminating the sample surface with a He-Ne laser. While scanning the device area with the focused laser the RTN is influenced at one well-defined spot only. We associate this spot with a filament of less than 1 μm2 in size that carries a large fraction of the current through the device and argue that the current is controlled by the charging and discharging of a single defect in proximity to this filament via Coulomb blocking resulting in the observed RTN. In different samples distributions of switching times for capture and emission of electrons at a single defect are measured as a function of applied voltage and temperature. Based on these data different configurations of the defect located in the nitride barrier are discussed within a model of an acceptorlike trap with a strong electron-lattice coupling which exchanges charge with the adjacent n+-type a-Si:H layers. © 1993 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.analys

Analysis of the moving photocarrier grating technique for semiconductors of high defect density - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review B, 2001)
The moving photocarrier grating (MPG) technique allows us to determine the carrier drift mobilities and the recombination lifetime of semiconductors. This technique utilizes a spatially and temporally modulated light intensity for the generation of photocarriers, which leads to a modulation of the carrier densities. The different mobilities of electrons and holes introduce a phase shift between the charge distributions. The resulting internal electric field produces a short circuit current which depends on the modulation frequency. The theoretical calculation of that short circuit current includes the diffusion and drift currents, and the generation and recombination processes. In the original treatment of the MPG method recombination between electrons and holes was assumed to proceed only through band-to-band transitions. We analyze here the MPG method by explicitly considering recombination through dangling bond states. We simulate short circuit current curves and compare them with measurements. The inclusion of recombination through dangling bonds allows us to explain an apparent contradiction in the evolution of the recombination lifetime as a function of light-induced degradation.

Analysis of the moving-photocarrier-grating technique for the determination of the mobility and lifetime of photocarriers in semiconductors - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review B, 1995)
We describe a technique for the determination of the carrier lifetime (τ) and the carrier mobilities (μn,μp) in semiconductors, namely the moving-photocarrier-grating method. This technique utilizes a moving intensity grating that is generated by the superposition of frequency shifted laser beams for the illumination of the sample. This results in a spatial and temporal modulation of the generation rate of photoelectrons and holes and, as a consequence, in a modulation of the photocarrier densities. The amplitudes and phases of the resulting carrier densities, space charges, and electric fields are calculated by solving the continuity and Poisson equations in the small signal approach. Their dependence on grating velocity and grating period are analyzed in the lifetime and the relaxation-time regimes. It is shown that a dc short circuit current jsc results from the action of space charge induced fields on the photogenerated electrons and holes that can be measured in an external circuit. The validity of this analysis is demonstrated by comparing the expression for jsc with data obtained for two a-Si:H samples that realize the lifetime and the relaxation-time regimes, respectively. Good fits are obtained over a wide range of grating periods and grating velocities for material parameters μn, μp, and τ that compare favorably with values obtained from other measurements. © 1995 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.IAP.exphys.analys

Atomic and electronic structure of few-layer graphene on SiC(0001) studied with scanning tunneling microscopy and spectroscopy - Lauffer, Peter; Emtsev, Konstantin; Graupner, Ralf; Ley, Lothar; Seyller, Thomas; Reshanov, Sergey; Weber, Heiko B. (Physical Review B, 2008)
Epitaxial growth of graphene on SiC surfaces by solid state graphitization is a promising route for future development of graphene based electronics. In the present work, we have studied the morphology, atomic scale structure, and electronic structure of thin films of few-layer graphene (FLG) on SiC(0001) by scanning tunneling microscopy and spectroscopy (STS). We show that a quantitative evaluation of the roughness induced by the interface is a tool for determining the layer thickness of FLG. We present and interpret thickness dependent tunneling spectra, which can serve as an additional fingerprint for the determination of the layer thickness. By performing spatially resolved STS, we find evidence that the charge distribution in bilayer graphene is inhomogeneous. © 2008 The American Physical Society.
UnivIS-Import:2015-04-14:Pub.2008.nat.dphy.IAP.LAP.atomic

Atomic layer deposited aluminum oxide films on graphite and graphene studied by XPS and AFM - Speck, Florian; Ostler, Markus; Röhrl, Jonas; Emtsev, Konstantin; Hundhausen, Martin; Ley, Lothar; Seyller, Thomas (Physica Status Solidi (C) Current Topics in Solid State Physics, 2010)
Epitaxial graphene (EG) grown by solid-state decomposition of SiC is a promising material for future graphenebased electronics. On EG, the fabrication of a field-effect device requires the deposition of suitable gate insulator. Atomic layer deposition (ALD) of aluminum oxide might be useful for this purpose. Therefore, we investigated the growth of ALD-Al 2O 3 on highly oriented pyrolytic graphite (HOPG) and EG by atomic force microscopy (AFM), photoelectron spectroscopy (XPS) and Raman spectroscopy. Water as oxidant in the ALD process leads to inhomogeneous nucleation, whereas ozone leads to the formation of closed oxide layers. However, significant degradation of the EG takes place at higher temperatures and ozone exposure as witnessed by XPS and Raman spectroscopy. Careful adjustment of the process parameters allows reducing the damage to a level undetectable in XPS while providing enough nucleation centers for the formation of a closed Al 2O 3 film potentially suitable as a gate insulator. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.exphys.atomic

Attosecond-fast internal photoemission - Heide, Christian; Hauck, Martin; Higuchi, Takuya; Ristein, Jürgen; Ley, Lothar; Weber, Heiko B.; Hommelhoff, Peter (Nature Photonics, 2020)
The photoelectric effect has a sister process relevant in optoelectronics called internal photoemission1,2,3. Here an electron is photoemitted from a metal into a semiconductor4,<a title="Di Bartolomeo, A. Graphene Schottky diodes: an experimental review of the rectifying graphene/semiconductor heterojunction. Phys. Rep. 606, 1–58 (2016)." href="https://www.nature.com/articles/s41566-019-0580-6#ref-CR5">5. While the photoelectric effect takes place within less than 100 attoseconds (1 as = 10−18 seconds)6,7, the attosecond timescale has so far not been measured for internal photoemission. Based on the new method CHArge transfer time MEasurement via Laser pulse duration-dependent saturation fluEnce determinatiON—CHAMELEON—we show that the atomically thin semimetal graphene coupled to bulk silicon carbide, forming a Schottky junction, allows charge transfer times as fast as (300 ± 200) as. These results are supported by a simple quantum mechanical model simulation. With the obtained cut-off bandwidth of 3.3 PHz (1 PHz = 1015 Hz) for the charge transfer rate, this semimetal/semiconductor interface represents a functional solid-state interface offering the speed and design space required for future light-wave signal processing.<br
Keywords: Nonlinear optics; Optical properties and devices; Optoelectronic devices and components; Ultrafast photonics

Band diagrams of intrinsic and p-tye diamond with hydrogenated surfaces - Ristein, Jürgen; Ley, Lothar; et al. (physica status solidi (a), 2003)
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.IAP.exphys.banddi

Bipolar treatment of the electrically detected transient grating technique - Hundhausen, Martin; Ley, Lothar (Applied Physics Letters, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.IAP.exphys.bipola

Calculating the Universal Energy Level Alignment of Organic Molecules on Metal Oxides - Ley, Lothar; Smets, Yaou; Pakes, Christopher I.; Ristein, Jürgen (Advanced Functional Materials, 2013)
Recently, Greiner et al. [Nat. Mater. 2012, 11, 76] published a survey of the level alignment of about 40 metal oxide/organic molecule interfaces. They observed a striking regularity in the electronic level alignment of the highest occupied molecular orbital (HOMO) and the Fermi level that depends solely on the difference between the substrate work function and the ionization energy of the molecule independent of the details of the electronic structure of the oxide. The authors could reproduce their data under the assumption of thermodynamic equilibrium occupation of the HOMO using four adjustable parameters. A model that quantifies well-established concepts in heterojunction physics and achieves the same result without any adjustable parameters is presented here. This approach explains why the level alignment is rather independent of the experimental details, such as the electronic structure of the oxide, defects in the oxide, and the thickness of oxide and overlayer. The model can also be extended to organic molecules or polymers on metals without any intermediate oxide as long as certain conditions are met. It also sheds new light on the large polaronic binding energy required to interpret the electronic level alignment of metal-polymer interfaces. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2013.nat.dphy.IAP.exphys.calcul
Keywords: energy-level alignment; full theory; organic electronics

Carrier Mobility and Lifetime in a-Si:H determined by the Moving Grating Technique - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
We have applied the moving grating technique (MGT) to amorphous silicon (a-Si:H) in order to determine the electron and hole mobilities and their lifetime. In this technique a short circuit current is induced by an interference grating moving with an adjustable velocity across the sample. The continuity equations for electrons and holes and Poisson's equation are solved to derive a theoretical expression for the short circuit current. We fit this expression to experimental data of the short circuit current as a function of the velocity and spatial period of the grating and obtain good agreement between theory and experiment. The electron mobility and the lifetime obtained from this fit is 7.7·10-2cm2/Vs and 2.1·10-6s, respectively, whereas the hole mobility is 15 times smaller than that for the electrons. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.carrie

Carrier Recombination in Doping-Superlattices of a-Si:H - Hundhausen, Martin; Ley, Lothar; et al. (Proc. 17th Int. Conf. on the Physics of Semiconductors, 1984)
UnivIS-Import:2015-04-16:Pub.1984.nat.dphy.IAP.exphys.carrie

Carrier recombination kinetics in amorphous doping superlattices - Ley, Lothar; Hundhausen, Martin (Disordered semiconductors, 1987)
Research activities on nipi structures are reported, along with conductivity measurements as a function of layer thickness. The salient features of these measurements are discussed. The authors consider the kinetics of photocarrier recombination in nipi samples below 20 K, as well as persistent photoconductivity.
UnivIS-Import:2015-04-17:Pub.1987.nat.dphy.IAP.exphys.carrie

Carrier Recombination Times in Amorphous-Silicon Doping Superlattices - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review Letters, 1984)
Doping superlattices, i.e., multilayer structures consisting of ultrathin (50 < d< 400 ) n-type, intrinsic, and p-type layers of a-Si: H (nipi structures), have been produced. Up to a tenfold increase in their infrared photoconductivity after band-gap illumination compared to unstructured a-Si: H is observed. The results are well described by a simple model for the carrier recombination kinetics that takes into account the spatial separation of electrons and holes due to the modulation of the band energies. © 1984 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1984.nat.dphy.IAP.exphys.carrie_2

Changes of the occupied density of defect states of a-Si:H upon illumination - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1996)
We study the light-induced transient changes of the near surface density of occupied states g(E) of undoped and boron-doped a-Si:H with photomodulated total photoelectron yield spectroscopy. The data show an increase of g(E) upon illumination between 0.35 eV above E F and 0.7 eV below E F (towards the valence band) and a decrease in the region of deep valence-band-tail states. The difference signal depends sublinearly on the laser intensity and reaches a maximum of Δg ≈ 10 17 cm -3 eV -1 at a laser intensity of 30 mW cm -2 (λ=532 nm). Time-resolved measurements reveal rise and decay times of the order of milliseconds. The experimental results are explained quantitatively by a recombination model. In the framework of this model, a range of deep defects around mid-gap energy are singly occupied and neutral at probe-light intensities. Additional illumination with a laser leads to double occupation of these defects and a decrease of the valence-band-tail occupation.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.change

Characteristics of solution gated field effect transistors on the basis of epitaxial graphene on silicon carbide - Ristein, Jürgen; Zhang, Wenying; Speck, Florian; Ostler, Markus; Ley, Lothar; Seyller, Thomas (Journal of Physics D-Applied Physics, 2010)
A solution gated field effect transistor has been fabricated on epitaxial single-layer graphene on 6H-SiC(0 0 0 1). Output and transfer characteristics were systematically studied as a function of electrolyte pH. The transfer characteristics of the device show a pH dependent shift of 19 ± 1 mV/pH. From the minimum sheet conductivity observed, an average charge carrier mobility of 1800 ± 100 cm 2 V -1 s -1 at room temperature has been inferred. It turns out that the Fermi level in the graphene layer is strongly pinned in the vicinity of the Dirac point. The analysis of the transfer characteristics is consistent with a concentration of 4 × 10 14 cm -2 interface states at 0.1 eV below the Dirac energy that is presumably associated with the (6√3 × 6√3)R30°-reconstruction at the interface between SiC(0 0 0 1) and graphene. © 2010 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.exphys.charac

Characterization of cubic bulk SiC and temperature induced polytype conversion in cubic CVD SiC studied by Raman spectroscopy - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Applied Physics, 2004)
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.IAP.LAP.charac

Characterization of defects in silicon carbide by Raman spectroscopy - Hundhausen, Martin; Püsche, Roland; Röhrl, Jonas; Ley, Lothar (physica status solidi (b), 2008)
We demonstrate the application of Raman spectroscopy as an optical non-contact method for the characterization of silicon carbide (SiC). The Raman spectra provide information about the polytype and thus can give direct information about microscopic inclusions of hexagonal polytypes in 3C-SiC grown by chemical vapor deposition (CVD) after annealing at elevated temperatures. Polytype conversion sets in at a about 1700°C and at higher temperatures eventually results in larger domains of 6H-SiC where twin boundaries act as barriers against a complete polytype conversion. We study shallow donor states of phosphorus- and nitrogen-doped SiC using low temperature electronic Raman spectroscopy. The various low frequency transitions observed in nitrogen doped SiC are assigned to the valley-orbit transitions of electrons in the 1s-ground states of donors that occupy inequivalent lattice sites. During vacuum annealing at elevated temperature graphitization of the SiC surface occurs. Raman spectroscopy is used to verify that under well controlled conditions a monoatomic graphene layer exists. We observe a phonon hardening of that layer compared to free standing graphene that we ascribe mainly to strain induced by different thermal expansion coefficients of graphite and SiC. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.IAP.exphys.charac

Characterization of oxidized SWCNTs by XPS - Holzinger, Michael; Hirsch, Andreas; Hennrich, Frank; Kappes, Manfred; Dziakova, Andrea; Ley, Lothar; Graupner, Ralf (Structural and Electronic Properties of Molecular Nanostructures, 2002)

Characterization of superlattices based on amorphous silicon - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Applied Physics, 1986)
UnivIS-Import:2015-04-14:Pub.1986.nat.dphy.IAP.exphys.charac

Charge transfer doping of Silicon - Rietwyk, K. J.; Smets, Y.; Bashouti, M.; Christiansen, S. H.; Schenk, A.; Tadich, A.; Edmonds, M. T.; Ristein, Jürgen; Ley, Lothar; Pakes, C. I. (Physical Review Letters, 2013)
UnivIS-Import:2015-03-09:Pub.2013.nat.dphy.IAP.exphys.charge

Comment on "Effect of average grain size on the work function of diamond films" - Ristein, Jürgen; Ley, Lothar (Applied Physics Letters, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.IAP.exphys.commen

Comment on quantum confinement effect in diamond nanocrystals studied by x-ray-absorption spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review Letters, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.commen

Correlation between electronic micro-roughness and surface topography in two-dimensional surface conducting hydrogen-terminated diamond - Yianni, Steve A.; Creedon, Daniel L.; Schenk, Alex K.; Xing, Kaijian; Akhgar, Golrokh; Hoxley, David I.; Ley, Lothar; McCallum, Jeffrey C.; Pakes, Christopher I. (Diamond and Related Materials, 2021)
The influence of surface topography on phase coherent transport in the two-dimensional (2D) hole band of surface transfer doped hydrogen-terminated (100) diamond is investigated. Low-temperature magneto-conductance measurements were carried out with an applied in-plane magnetic field to quantify the effect of electronic micro-roughness on spin dephasing in the 2D hole band for Hall bar devices with similar transport characteristics, but significantly different topographic roughness. The electronic micro-roughness of the 2D hole band, described by the parameter d2L, where d is the root-mean-square (rms) fluctuation in the width of the quantum well and L is the correlation length of the fluctuations, is found to increase for surfaces with increased roughness. Fluctuations in the well width likely arise from a locally varying hole carrier density, arising for example from a local variation in the concentration of ionic components in the surface water layer.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Diamond; Phase coherent backscattering; Weak anti-localisation; Weak localization

Covalent Functionalization of Arc Discharge, Laser Ablation and HiPCO Single‐Walled Carbon Nanotubes - Abraham, Jürgen; Whelan, Paul; Hirsch, Andreas; Hennrich, Frank; Kappes, Manfred; Samaille, Damien; Bernier, Patrick; Vencelová, Andrea; Graupner, Ralf; Ley, Lothar (Molecular Nanostructures, 2003)

Cross-Sectional Scanning Tunneling and Scanning Force Microscopy of Amorphous Hydrogenated Silicon pn-Doping-Superlattices in Nitrogen and Air - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Vacuum Science & Technology B: Microelectronics Processing and Phenomena, 1994)
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.IAP.exphys.crosss

Cross-sectional scanning-tunneling-spectroscopy of a-Si:H pn-doping superlattices - Hundhausen, Martin; Ley, Lothar; et al. (Superlattices and Microstructures, 1994)
The electronic properties of amorphous hydrogenated silicon (a-Si:H) pn-doping-superlattices are investigated by cross-sectional current imaging tunneling spectroscopy (CITS) using a scanning tunneling microscope in dry nitrogen ambient. In the constant current mode a contrast between n- and p-type layers is found. In addition, the spatially resolved normalized differential conductivity is measured for different bias voltages applied to the sample with respect to the STM tip. For small bias voltage at which tunneling occurs between the tip and gap-states of the amorphous superlattice a contrast between p-type and n-type doped layers is observed in the normalized differential conductivity. This is in agreement with the different densities of states available for tunneling between the STM and the differently doped layers. However, the contrast is almost missing if a larger voltage is applied, so that tunneling mainly occurs between tip and sample band-states.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.IAP.exphys.crosss_7

Defect Spectroscopy and Determination of the Electron Diffusion Length in Single Crystal Diamond by Total Photoelectron Yield Spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review Letters, 1997)
Novel photoelectron yield experiments performed with a dynamical range of 8 orders of magnitude reveal a new excitation channel for electron emission on diamond (100) and (111) surfaces with negative electron affinity which is due to defect states 2.0 and 4.1 eV below the conduction hand minimum. Analyzing the competition of free conduction band electrons excited out of defects and excitons with respect to final photoelectron production we determine that the electron diffusion length in p-type IIb diamond is between 150 and 250 μm.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.IAP.exphys.defect

Dehydrogenation and the surface phase transition on diamond (111): kinetics and electronic structure - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1999)
The (1×1) to (2×1) surface phase transition of the hydrogen-covered diamond (111) surface is investigated by core level spectroscopy, low-energy electron diffraction, and measurements of the electron affinity. The latter method is shown to be a reliable measure of the hydrogen coverage. Prolonged annealing of the surface at 1000 K converts the hydrogen-terminated (1×1) structure with an electron affinity of -1.27 eV to a hydrogen-free (2×1) reconstruction, increases the separation of valence-band maximum from the Fermi level EF from 0.68 to 0.88 eV, and results in a positive electron affinity of +0.38 eV. Annealing the surface at high temperature (up to 1400 K) yields the same (2×1) surface structure albeit with an increase in the separation of the valence-band maximum from EF to 1.42 eV and a positive electron affinity of 0.8 eV which is associated with a partial surface graphitization. An analysis of the kinetics of the thermally induced hydrogen desorption yields an activation energy of 1.25±0.2eV. It was found that hydrogen desorption and reconstruction are surface phase transitions which are not directly linked. Instead, an intermediate phase with a high concentration of dangling bonds (up to 70%) is observed. The (1×1) to (2×1) phase transition is phenomenologically well described by a first-order transition provided a critical density of dangling bonds of about 70% is included in the analysis in such a way that the rate constant for reconstruction vanishes below that value. © 1999 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.dehydr

Deriving the kinetic parameters for Pt-silicide formation from temperature ramped in situ ellipsometric measurements - Hundhausen, Martin; Ley, Lothar; et al. (Thin Solid Films, 2000)
Single-wavelength ellipsometry is employed to monitor in situ the reaction of 23 nm platinum layers with Si(100) to form platinum silicides during heating at constant rates up to 100 K/min. A previous study showed that by the use of 'Kissinger' plots the activation energy of the intermediate silicide phase Pt2Si and that of the final PtSi can be determined with an accuracy of 50 meV. It is the purpose of the present paper to extend the study one step further and obtain also the pre-exponential growth factor by directly modeling the evolution of the ellipsometric data as they were obtained during the temperature ramp. To do so, the chemical composition of the reaction products and the thickness of the formed layers were identified at crucial stages of the reaction via RES. Additionally, the optical constants of the constituent phases Pt, Pt2Si and PtSi were calculated from spectroscopic ellipsometry measurements in the range from 1.5 to 4.5 eV. With this input information the evolution of the ellipsometric angles during the reaction of Pt and Si were modeled quantitatively. The analysis yields good fits to the data for different ramp rates with activation energies of 1.50 and 1.70 eV and reaction coefficients of 37 and 27 cm(2)/s for the Pt/Si to Pt2Si and Pt2Si to PtSi formation, respectively. A significant improvement of the fit is obtained when the activation energies are allowed to be distributed about their mean value with a width of 47 meV. This distribution takes inhomogeneities in the reaction process into account and leads to a broadening of the reaction fronts. (C) 2000 Elsevier Science S.A. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.derivi
Keywords: ellipsometry; optical properties; reaction kinetics; silicides

Development of a silicon-diamond interface on (111) diamond - Schenk, A. K.; Sear, M. J.; Dontschuk, N.; Tsai, A.; Rietwyk, K. J.; Tadich, A.; Cowie, B. C.C.; Ley, Lothar; Stacey, A.; Pakes, C. I. (Applied Physics Letters, 2020)
We report the preparation of a silicon terminated (111) diamond surface. Low energy electron diffraction and core level photoemission demonstrate that this surface is highly ordered and homogeneous and possesses a negative electron affinity. Our analysis suggests that the surface reconstruction begins with the formation of silicon trimers that coalesce into a rhombohedral 2D silicon layer reminiscent of rhombohedral silicene.
CRIS-Team Scopus Importer:2020-03-06

Diamond growth during the bias pretreatment in microwave CVD of diamond - Ristein, Jürgen; Hundhausen, Martin; Ley, Lothar; et al. (Diamond and Related Materials, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.IAP.exphys.diamon

Diamond surface conductivity experiments and photoelectron spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 2001)
A unique feature of diamond surfaces is a highly conductive p-type layer which is usually observed when the surfaces are hydrogen terminated. We present a combination of conductivity and photoelectron yield measurements on a variety of different diamond samples in order to elucidate the role of hydrogen and adsorbates for this phenomenon. The experiments show that hydrogen termination is a necessary but not a sufficient condition for the appearance of the surface conductivity. Additionally, adsorbates from the atmosphere are needed. On the basis of the experiments an electrochemical model is developed which can explain the effect of the hydrogen termination and also shows why hydrogen terminated diamond is the only semiconductor with p-type surface conductivity. © 2001 Elsevier Science. B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.diamon
Keywords: Diamond; Surface; Surface conductivity

Diamond Surfaces - Ley, Lothar; Ristein, Jürgen (Surface and Interface Science, 2012)
UnivIS-Import:2015-04-20:Pub.2012.nat.dphy.IAP.exphys.diamon

Diamond surfaces with air-stable negative electron affinity and giant electron yield enhancement - O'Donnell, Kane M.; Edmonds, Mark T.; Ristein, Jürgen; Tadich, Anton; Thomsen, Lars; Wu, Qi-Hui; Pakes, Chris I.; Ley, Lothar (Advanced Functional Materials, 2013)
The presence of an air-stable negative electron affinity (NEA) on lithium-covered oxygen-terminated diamond after a thermal activation process is demonstrated. The NEA is unequivocally established by the onset of photoelectron yield at the bandgap energy of 5.5 eV. This surface exhibits a secondary electron yield enhancement by a factor of 200, compared to a surface with positive electron affinity. The surface chemistry leading to the necessary surface dipole was elucidated by core-level photoemission spectroscopy in conjunction with previous theoretical calculations. The insensitivity to the details of the deposition process opens a route to practical and robust negative-electron affinity devices based on diamond. A robust, air-stable negative electron affinity diamond surface with giant secondary electron yield enhancement is introduced. Starting with oxidized diamond (100), lithium deposition and annealing induce a structural and electronic change to a negative electron affinity surface showing electron yield enhancement greater than 200. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2013.nat.dphy.IAP.exphys.diamon
Keywords: diamond; electron emission; lithiation; negative electron affinity; surface modification

Disappearance of the LO-Phonon line in the Raman spectrum of 6H-SiC - Hundhausen, Martin; Ley, Lothar; et al. (Materials Science Forum, 2000)
We undertook a study of the intensities of optical vibrational modes in the Raman spectrum of 6H-SiC as a function of excitation energy between 2.4 eV and 4.9 eV. A disappearance of the LO0 mode which is the longitudinal optical mode with the highest frequency is observed at 4.38 eV. The result is explained in the framework of a bond-Raman-polarizability model for the Raman scattering cross section as due to the cancellation of the energy dependent bond-Raman polarizabilities of intra- and inter-bilayer bonds that connect the Si and C planes in SiC.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.disapp

Dispersion of surface states on diamond (100) and (111) - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1997)
We present angle-resolved photoelectron spectra and surface state dispersions for the clean, 2x1 reconstructed (111) and (100) surfaces of diamond. For the (100) surface a surface state is found in the gap of the projected bulk band structure around Ȳ, which has a binding energy of 2.7 eV at Ȳ (relative to the Fermi level) and a dispersion in the Γ̄-Ȳ direction of 0.5 eV, consistent with theory. At Γ̄ a surface resonance is observed at 1.4 eV binding energy. No surface states were observed above the valence-band maximum. Our results on the (111) surface show a strongly dispersing surface state that reaches its maximum 0.5 eV below the Fermi level at K̄. This result implies a gap of at least 0.5 eV in the surface electronic structure, which has consequences for the surface reconstruction in terms of a π-bonded chain model.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.IAP.exphys.disper

Doping of single-walled carbon nanotube bundles by Brønsted acids - Graupner, Ralf; Abraham, Jürgen; Vencelová, Andrea; Seyller, Thomas; Hennrich, Frank; Kappes, Manfred; Hirsch, Andreas; Ley, Lothar (Physical Chemistry Chemical Physics, 2003)
Using X-ray induced photoelectron spectroscopy, the influence of Brønsted acids, namely sulfuric, nitric, and hydrochloric acid on the electronic properties of single-walled carbon nanotubes (SWCNTs) was investigated. Doping effects were monitored by changes in binding energy of the C 1s core level of the nanotubes. For all three acids, an acceptor type doping of the SWCNTs was observed by a shift of the C 1s core level towards lower binding energies. The inferred change of the Fermi-level position was 0.5 eV in the case of HSO, 0.2 eV in the case of HNO, and 0.1 eV in the case of HCl. For HNO and HCl the doping was found to be unstable. The S 2p, N 1s, and Cl 2p core level spectra of the corresponding acid showed spectral features which can be attributed to the respective oxidation state of these anions in the acid, indicating that doping was induced by intercalation.

Effektive correlation energies for defects in a-C:H from a comparison of photoelectron yield and electron spin resonance experiments - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.IAP.exphys.effekt

Electrochemical surface transfer doping: the mechanism behind the surface conductivity of hydrogen terminated diamond - Ristein, Jürgen; Ley, Lothar; et al. (Journal of The Electrochemical Society, 2004)
Intrinsic diamond with a bandgap of 5.4 eV exhibits a surface conductivity (SC) of the order of 10-5 Ω-1 when terminated by hydrogen. This conductivity is carried by a hole-accumulation layer close to the surface with an areal carrier concentration of about 1013 cm -2, and it has already been utilized for a unique kind of field effect transistor [H. Kawarada, Surf. Sci. Rep., 26, 205 (1996)]. Although the microscopic doping mechanism is still under debate. Based on the results of a variety of surface-sensitive experiments we propose a new surface-transfer doping mechanism by which electron transfer from the valence band to adsorbed, hydrated ionic species at the surface creates the holes for the surface conductivity. In order to draw a complete picture of the surface conductivity concepts from surface and semiconductor physics as well as electrochemistry have to be adopted. © 2004 The Electrochemical Society. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.IAP.exphys.electr

Electron affinity and band bending of the single crystal diamond (111) surface - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 1999)
The electron affinity and band bending of a single crystal diamond (111) surface have been investigated as a function of hydrogen coverage via work function measurements, photoelectron yield spectroscopy, X-ray-excited photoelectron spectroscopy (XPS), and low-energy electron diffraction (LEED). The hydrogen desorption and the 1×1-2×1 surface phase transition were achieved by electron-beam irradiation at room temperature as well as annealing at high temperature. The electron affinity ranges from -1.27 eV for the fully hydrogen-covered 1×1 surface to 0.38 eV for the hydrogen-free 2×1 reconstructed surface. Electron beam irradiation is demonstrated to be an effective method to induce hydrogen desorption and surface reconstruction. However, this irradiation process does not change the surface band bending on type IIb diamond, which is generally increased by annealing. It is concluded that the electron-affinity change is caused by the C-H dipole layer, whereas the band bending is not directly related to hydrogen coverage or reconstruction but rather due to charged surface defects that are created simultaneously with the thermal treatment.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.electr_2
Keywords: Diamond; Electron affinity; Photoelectron emission spectroscopy; Surface band bending

Electron affinity of plasma-hydrogenated and chemically oxidized diamond (100) surfaces - Ristein, Jürgen; Maier, Florian; Ley, Lothar (Physical Review B, 2001)
The electron affinity (EA) χ of single crystal diamond (100) is determined as a function of hydrogen and oxygen coverage by a combination of work function and photoemission experiments. For the fully hydrogenated (100)-(2×1):H surface an EA of -1.3 eV and for the oxidized surface C(100)-(1×1):O χ = +1.7 eV are obtained. These are the lowest and the highest electron affinities, respectively, ever reported for any diamond surface. The variation in χ with O and H coverage is well described by a simple dipole model provided that the depolarization is properly taken into account for high adsorbate densities. This analysis favors the bridge position (etherlike) for oxygen on C(100). By mixing H and O adsorbates on a microscopic scale the EA of C(100) can be adjusted at will over 3 eV between the extreme values without jeopardizing the chemical passivation of the diamond surface afforded by H or O termination.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.electr

Electron affinity of the bare and hydrogen covered single crystal diamond (111) surface - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review Letters, 1998)
The electron affinity chi and the band diagram of single crystal diamond (111) surfaces was determined as a function of hydrogen coverage by combining work function measurements with photoelectron yield and core level photoemission spectroscopy. chi ranges from -1.27 eV for the fully hydrogen covered (1 X 1) surface to +0.38 eV for the hydrogen free (2 X 1) reconstructed surface. This change is quantitatively explained by a surface dipole model provided a coverage dependent depolarization is included. The dipole moment of the C-H bond on diamond (111) is found to be 0.09 e Angstrom.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.IAP.exphys.theele

Electronic and chemical passivation of hexagonal 6H-SiC surfaces by hydrogen termination - Ristein, Jürgen; Ley, Lothar; et al. (Applied Physics Letters, 2001)
Hydrogenation of 6H-SiC (0001) and (0001̄) is achieved by high-temperature hydrogen treatment. Both surfaces show a low-energy electron diffraction pattern representative of unreconstructed surfaces of extremely high crystallographic order. On SiC(0001), hydrogenation is confirmed by the observation of sharp Si-H stretching modes. The absence of surface band bending for n-and p-type samples is indicative of electronically passivated surfaces with densities of charged surface states in the gap of below 7 × 1010 cm-2 for p-type and 1.7 × 1012 cm-2 for n-type samples, respectively. Even after two days in air, the surfaces show no sign of surface oxide in x-ray photoelectron spectroscopy. © 2001 American Institute of Physics.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.electr_2

Electronic and structural properties of the a-Si:H/a-SiNx:H interface - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
Valence band offsets and band bending were systematically investigated by photoelectron spectroscopy for the a-Si:H/a-SiNX:H heterojunction covering nitrogen concentrations between 0≤×≤1.63. The chemical structure and the defect density of the interfaces are determined. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.electr

Electronic and structural properties of the interface between c-Si (111) and diamond like carbon - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 1997)
The chemical and electronic structure of the interface between crystalline silicon- and diamond-like amorphous hydrogenated carbon (a-C:H) are investigated. Employing in situ photoelectron spectroscopy the formation of the interface between both materials is observed step by step in terms of chemical composition as well as in terms of band bending and band offset evolution. When the heterostructure is completed a stoichiometric SiC interface layer with a thickness of 18 Å has formed whose valence band maximum lies 0.28 eV below that of the silicon substrate and 0.4 eV above that of the a-C:H overlayer. © 1997 Elsevier Science S.A.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.IAP.exphys.electr_6
Keywords: Band bending; Band offset; c-Si:a-C:H interface; Photoelectron spectroscopy

Electronic properties of single crystalline diamond surfaces - Ley, Lothar; Ristein, Jürgen; et al. (Carbon, 1999)
Key parameters of the surface electronic structure of diamond (111), such as surface core level shifts, surface state dispersion, band bending, and electron affinity, are presented and discussed. The first actual value for the negative electron affinity of diamond (111):H 1×1 is measured as χ = -1.27 eV. A model is given that describes the variation in χ with hydrogen coverage quantitatively in terms of C-H bond dipoles.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.electr_8

Electronic Raman Studies of Shallow Donors in Silicon Carbide - Püsche, Roland; Hundhausen, Martin; Ley, Lothar; Semmelroth, Kurt; Pensl, Gerhard; Desperrier, Patrick; Wellmann, Peter; Haller, Eugene E.; Ager, J.W.; Starke, Ulrich (Materials Science Forum, 2006)
We study electronic Raman scattering of phosphorus and nitrogen doped silicon carbide (SiC) as a function of temperature in the range 7 K < T < 300K. We observe a series of peaks in the Raman spectra which we assign to electronic transitions at nitrogen and phosphorus donors on different lattice sites. These transitions are identified as valley orbit transitions of the Is donor ground state. From the polarization dependence of the observed peaks, we find that all electronic Raman signals have E2-symmetry of C 6v for the hexagonal polytypes (6H-SiC and 4H-SiC) and E-syinmetry of C3., for 15R-SiC. Wc find a reduction of the intensities of all valley-orbit Raman signals with increasing temperature and ascribe this reduction to the decreasing occupation of donor state
UnivIS-Import:2015-04-14:Pub.2006.nat.dphy.IAP.LAP.electr
Keywords: Doping; Nitrogen-donor; Phosphorus-donor; Raman spectroscopy

Electronic states of an ordered oxide on C-terminated 6H-SiC - Maier, Florian; Ristein, Jürgen; Ley, Lothar; et al. (Surface Science, 1999)
An ordered oxide monolayer with (√3×3√3)R30° periodicity was obtained on carbon-terminated 6H-SiC(000̄3) after preparation with a hydrogen microwave plasma. The stoichiometry of this surface was investigated by X-ray-induced photoelectron spectroscopy. Most components of the Si 2p, C 1s, and O 1s core lines are in agreement with the recently published atomic structure of this ordered monolayer. Beyond this we found hydrocarbon contamination that could be removed by annealing, and small graphitized areas remaining on the surface. We used angle-resolved ultra-violet photoelectron spectroscopy to examine the electronic structure of the valence band. Besides the O 2s and the O 2p lone pair state at 24 eV and 6 eV respectively below the valence band maximum (VBM), we detected a dangling bond state slightly above the VBM and a Si hybrid-O 2p-derived bonding state dispersing between 9.1 and 11.0 eV below the VBM. For the dangling bond state the possibility of a Mott-Hubbard ground state is discussed. In order to clarify the origin of the oxygen-derived states our results are compared with previous investigations of silicon oxides.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.electr

Electronic structure and defect density of states of hydrogenated amorphous carbon (a-C:H) as determined by photoelectron and photoelectron yield spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
Amorphous hydrogenated carbon films were prepared by RF-PECVD of CH4 with the self bias varying from 0 to 200V. The films were analysed with x-ray and ultraviolet photoelectron spectroscopy as well as photoelectron yield spectroscopy. The densities as derived from the plasmon energies increase from 1.2 to 1.7 g/cm3 with bias voltage and the sp2/(sp3+sp2) ratio extracted from an analysis of the valence band spectra increases from 15 to 35% over the same range. Two defect bands were identified in the pseudogap, 1.4 eV and 2.4 eV above the π-bonding states with integrated densities that increase from 1·1020 to 7·1020 cm-3 with bias. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.electr_5

Engineering the spin-orbit interaction in surface conducting diamond with a solid-state gate dielectric - Xing, Kaijian; Tsai, Alexander; Creedon, Daniel L.; Yianni, Steve A.; Mccallum, Jeffrey C.; Ley, Lothar; Qi, Dong-Chen; Pakes, Christopher I. (Applied Physics Letters, 2020)
Hydrogen-terminated (H-terminated) diamond, when surface transfer doped, can support a sub-surface two-dimensional (2D) hole band that possesses a strong Rashba-type spin-orbit interaction. By incorporating a V2O5/Al2O3 bilayer gate dielectric in a diamond-based metal-oxide-semiconductor architecture, metallic surface conductivity can be maintained at low temperature, avoiding the carrier freeze out exhibited by devices with an Al2O3 gate dielectric alone. Hole densities of up to 2.5x10(13)cm(-2) are achieved by the electrostatic gating of the device, and the spin-orbit interaction strength can be tuned from 3.5 +/- 0.5meV to 8.4 +/- 0.5meV, with a concurrent reduction in the spin coherence length from 40 +/- 1nm to 27 +/- 1nm. The demonstration of a gated device architecture on the H-terminated that avoids the need to cycle the temperature, as is required for ionic liquid gating protocols, opens a pathway to engineering practical devices for the study and application of spin transport in diamond.
CRIS-Team WoS Importer:2020-05-19

Experimental Determination of the Phonon-Eigenvectors of Silicon Carbide by Raman Spectroscopy - Hundhausen, Martin; Ley, Lothar; et al. (Materials Science Forum, 2002)
The phonon frequencies of silicon carbide (SiC) depend on the atomic masses of the constituent elements Si and C. In general, the frequency decreases, when the mass of one kind of atom is increased by isotopic substitution. Quantitatively, the shift of a phonon line in the Raman spectrum due to such a substitution depends on the phonon eigenvector of the isotopically modified constituent atom. We measure the frequency shifts for Raman active modes in SiC polytypes, when the 12C-isotope is replaced by 13C and calculate the absolute value of the eigenvector of the carbon sublattice from these results. With these results a validation and improvement of the force constants used in a linear-chain model to calculate phonon dispersion curves is possible. © 2002 Trans Tech Publications.
UnivIS-Import:2015-04-14:Pub.2002.nat.dphy.IAP.LAP.experi_5
Keywords: Phonon dispersion curves; Phonon eigenvectors; Raman spectroscopy

Experimental evidence for Phonon folding in compositional amorphous Superlattices - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1985)
We give experimental evidence for the folding of LA-phonons in a-Si:H/a-SiNx:H compositional superlattices with periods ranging from 60 to 400 Å. We observe two peaks between 5 and 70 cm-1 in the Raman spectra of these samples which we identify with transitions into the second and third branch of the folded longitudinal acoustic phonon dispersion curve. The dispersion of these branches was determined by varying the superlattice period and the laser frequency. The result is well described by a continuum theory that takes the differences in density and sound velocity of a-Si:H and a-SiNx:H into account. © 1985.
UnivIS-Import:2015-03-05:Pub.1985.nat.dphy.IAP.exphys.experi

Facile solubilization of single walled carbon nanotubes using a urea melt process - Jung, Adrian; Ford, William; Graupner, Ralf; Wessels, Jurina; Yasuda, Akio; Ley, Lothar; Hirsch, Andreas (Electronic Properties of Novel Nanostructures, 2005)
In this work we present a simple and effective process to overcome the water insolubility of mildly oxidized Single Walled Carbon Nanotubes (SWCNTs). As this insolubility mainly arises from strong van-der Waals and π-π stacking interactions of the nanotubes, we applied a urea-melt process to break up the bundles and simultaneously convert the carboxylic functional groups into primary amides. After intense washing and precipitation steps the urea functionalized nanotubes (U-SWCNTs) show a remarkably increased solubility in water and some alcohols which, makes them accessible for further functionalization and applications in these solvents. © 2005 American Institute of Physics.

Fermi level on hydrogen terminated diamond surfaces - Ristein, Jürgen; Ley, Lothar; et al. (Applied Physics Letters, 2003)
The characterization of hydrogen terminated patterns contacted with gold and aluminum on (100) diamond surface using atomic force microscopy was discussed. Taking into account the negative electron affinity of -1.3 eV and a band gap of 5.5 eV the Fermi energy was found to be 0.7 eV deep in the valence band.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.IAP.exphys.fermil

Field emission measurements with micrometre resolution on carbon nanostructures - Stammler, Martin; Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 1999)
The field emission properties of carbon nanostructures grown in a microwave plasma chemical vapour deposition system under bias conditions were investigated. Different carbon nanostructures, namely nanocrystalline diamond films (sample A) and nanotubes (sample B), were grown under conditions similar to those employed during the bias pretreatment for diamond growth. Morphological and structural properties of the carbon nanostructures were investigated by scanning electron microscopy, Raman and photoelectron spectroscopy. The field emission properties of the samples were measured by means of a field emission scanning microscope using resolutions of 3 and 40 μm, respectively. The local emission follows the Fowler-Nordheim law up to 1 mA/mm2 (3 mA/mm2) for sample A (sample B). Higher currents lead for sample A to an improved emission behaviour, while on sample B the application of higher currents can be detrimental in some cases. The average onset field strength (measured at a current of 0.5 nA) was as low as 55 V/μm (sample A) and 9 V/μm (sample B), respectively, compared with 200 V/μm and more for CVD diamond films.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.fielde
Keywords: Field emission; Nanocrystalline diamond; Nanotubes; Scanning electron microscopy

Field enhanced conductivity in a-Si:H thin film transistors - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
We have used amorphous silicon thin film transistors (TFT) to study the excitation and the distribution of electrons in the band tail states in the presence of strong electric fields at low temperature. The dark conductivity shows the same features as field enhanced conductivity (FEC) in doped a-Si:H, albeit at much smaller fields. The magnitude of the IR-photoconductivity measured between 120 and 260 meV is independent of gate or source-drain voltage as long as the source-drain current is kept constant. We consider a model in which electrons are excited by the field from the Fermi energy (EF) to an energy higher up in the band tail. The IR-photocurrent spectra reflect then the carrier distribution that results from the thermalization of electrons back to EF. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.fielde

Formation of the interface between c-Si(111) and diamond-like carbon studied with photoelectron spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Applied Surface Science, 1998)
The hydrogen-terminated Si(111) surface was used as a substrate to grow amorphous hydrogenated carbon (a-C:H) films by means of layer-by-layer plasma deposition. Electronic and structural properties of the forming interface were determined by in situ core level and valence band photoelectron spectroscopy. From the core level spectra the gradual formation of an initially carbon-rich and eventually stoichiometric silicon carbide interface layer is inferred with a final thickness of 18 Å. The silicon core level data indicate that the substrate is hydrogen-passivated owing to the plasma exposure. On the final heterostructure, the valence band edge of the diamond-like carbon is found to be 0.4 eV below that of the interfacial a-SiC:H and also below that of the silicon, with the offset amounting to 0.7 ± 0.1 eV. © 1998 Elsevier Science B.V.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.IAP.exphys.format
Keywords: Band bending; Band offset; Photoelectron spectroscopy; Silicon-carbon interface

Fuctionalization of single-walled carbon nanotubes with organo-lithium compounds: A combined XPS, STM, and AFM study - Graupner, Ralf; Abraham, Jürgen; Vencelová, Andrea; Lauffer, Peter; Ley, Lothar; Hirsch, Andreas (Electronic Properties of Novel Nanostructures, 2005)
A covalent sidewall functionalization of Single-Walled Carbon Nanotubes (SWCNTs) has been achieved by a reaction with butyllithium in benzene. The nucleophilic attack of the lithium organyl leads to a transfer of nagative charge to the SWCNTs which is balanced by the positive charge of the Li-ions. In our investigation we were able to verify the negative charge on the SWCNTs by a concomitant shift of the binding energy of the C 1s core levels of the SWCNTs in X-ray induced photoelectron spectroscopy (XPS). Moreover, scanning tunneling microscopy (STM) reveals a decoration of the tubewalls by features which exhibit the expected threefold symmetry of the butyl-groups. The charging of the SWCNTs in solution could also be verified by applying a homogeneous electric field using Au coated glass electrodes. The electrodes were chraracterized by XPS and atomic force microscopy (AFM). These measurements reveal the appearance of Li on one electrode, and the occurance of SWCNTs on the counter electrode. © 2005 American Institute of Physics.

Functionalization of single-walled carbon nanotubes by aromatic molecules studied by scanning tunneling microscopy - Lauffer, Peter; Jung, Adrian; Graupner, Ralf; Hirsch, Andreas; Ley, Lothar (physica status solidi (b), 2006)
A functionalization of single-walled carbon nanotubes (SWCNTs) without the necessity to introduce defects to the atomic structure of the graphitic lattice can be achieved via π-stacking interaction of the SWCNTs sidewalls with aromatic molecules. In our work we study the functionalization of SWCNTs with two different aromatic molecules by scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS Functionalization was performed in solution and the SWCNTs so obtained were transfered to a sputter-annealed Au(111) substrate using dry transfer techniques in vacuum to avoid surface contamination. Differential conductance imaging of the atomically resolved functionalized SWCNT reveals a substructure which can be attributed to the molecular orbitals of aminoanthracene. These findings are compared to the STM images obtained from the bare molecule prepared by thermal evaporation on a clean Au(111) surface which are interpreted with the help of quantum chemical calculations of the molecular orbital structure. © 2006 WILEY-VCH Verlag GmbH & Co. KGaA.

Functionalization of single-walled carbon nanotubes with (R-)oxycarbonyl nitrenes - Holzinger, Michael; Abraham, Jürgen; Whelan, Paul; Graupner, Ralf; Ley, Lothar; Hennrich, Frank; Kappes, Manfred; Hirsch, Andreas (Journal of the American Chemical Society, 2003)
Sidewall functionalization of single-walled carbon nanotubes (SWCNTs) via the addition of (R-)-oxycarbonyl nitrenes allows for the covalent binding of a variety of different groups such as alkyl chains, aromatic groups, dendrimers, crown ethers, and oligoethylene glycol units. Such additions lead to a considerable increase in the solubility in organic solvents such as 1,1,2,2-tetrachloroethane (TCE), dimethyl sulfoxide (DMSO), and 1,2-dichlorobenzene (ODCB). The highest solubilities of 1.2 mg/mL were found for SWCNT adducts with nitrenes containing crown ether of oligoethylene glycol moieties in DMSO and TCE, respectively. The presence of chelating donor groups within the addends allowed for the complexation of Cu and Cd. Atomic force microscopy (AFM) and transmission electron microscopy (TEM) revealed that the functionalized tubes form thin bundles with typical diameters of 10 nm. The presence of thin bundles in solution is supported by H NMR spectroscopy. The elemental composition of the functionalized SWCNT was determined by X-ray photoelectron spectroscopy (XPS). The use of Raman and electron absorption spectroscopy (UV/Vis-nIR) showed that the electronic properties of the SWCNTs are mostly retained after functionalization, indicating a low degree of addition within this series of SWCNT derivatives.

Geometry of the (2x1) reconstruction of diamond(111) - Heinz, Klaus; Maier, Florian; Ristein, Jürgen; Ley, Lothar; et al. (Journal of Physics: Condensed Matter, 2002)
UnivIS-Import:2015-04-14:Pub.2002.nat.dchph.lpc2._geome

G -factor and well-width fluctuations as a function of carrier density in the two-dimensional hole accumulation layer of transfer-doped diamond - Akhgar, Golrokh; Ley, Lothar; Creedon, Daniel L.; Stacey, Alastair; Mccallum, Jeffrey C.; Hamilton, Alex R.; Pakes, Christopher (Physical Review B, 2019)
The two-dimensional (2D) hole gas at the surface of transfer-doped diamond shows quantum-mechanical interference effects in magnetoresistance in the form of weak localization and weak antilocalization (WAL) at temperatures below about 5 K. Here we use the quenching of the WAL by an additional magnetic field applied parallel to the 2D plane to extract the magnitude of the in-plane g-factor of the holes and fluctuations in the well width as a function of carrier density. Carrier densities are varied between 1.71 and 4.35×1013cm-2 by gating a Hall bar device with an ionic liquid. Over this range, calculated values of |g| vary between 1.6 and 2.3 and the extracted well-width variation drops from 3 to 1.3 nm rms over the phase coherence length of 33 nm for a fixed geometrical surface roughness of about 1 nm as measured by atomic force microscopy. Possible mechanisms for the extracted variations in the presence of the ionic liquid are discussed.
CRIS-Team Scopus Importer:2019-08-02

Graphene layers on silicon carbide studied by Raman spectroscopy - Röhrl, Jonas; Hundhausen, Martin; Emtsev, Konstantin; Seyller, Thomas; Ley, Lothar (Materials Science Forum, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.IAP.exphys.graphe

Growth of 3C-SiC Bulk Material by the Modified Lely-Method - Krieger, Michael; Hundhausen, Martin; Ley, Lothar; et al. (Materials Science Forum, 2004)
The growth of cubic 3C-SiC single crystals by the modified Lely method is reported. Free-standing 200μm thick 3C-SiC epilayers were employed as seed crystals. The source material consisted of stoichiometric SiC; in addition, a separate Si source was deposited in the furnace at a temperature of about 1500°C. The temperature of the seed crystal was kept in the range of (1850-1950)°C. The growth rate is equal to 0.05mm/h and a nitrogen donor concentration of (2-6) ×1018 cm-3 is determined in the grown 3C-SiC.
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.IAP.LAP.growth_2
Keywords: 3C-SiC; Bulk growth; Modified Lely method

Growth of cubic SiC single crystals by the physical vapor transport technique - Semmelroth, Kurt; Krieger, Michael; Pensl, Gerhard; Nagasawa, H.; Püsche, Roland; Hundhausen, Martin; Ley, Lothar; Nerding, Melanie; Strunk, Horst Paul (Journal of Crystal Growth, 2007)
Suitable process parameters for the growth of cubic 3C-SiC single crystals via the seeded physical vapor transport (PVT) technique, also known as the modified Lely method, have been determined. Free-standing, 200 μm thick 3C-SiC epilayers with (0 0 1)- or (0 0 1̄)-face grown on undulant Si (0 0 1) as well as 3C-SiC platelets with [1 1 1]- or [1̄ 1̄ 1̄]-orientation grown by thermal decomposition of methyl trichlorosilane in hydrogen were employed as seed crystals. The source material consisted of stoichiometric SiC; in addition, a separate Si source was deposited in the furnace at a temperature of about 1500 °C. The temperature of the seed crystals was kept at about 1900 °C. Stable growth of 3C-SiC bulk material of high crystalline quality was reached on 3C-SiC seed crystals with (0 0 1)-face providing a low density of planar defects and at near-thermal-equilibrium conditions resulting in a reduction of internal stress and as a consequence in avoiding the generation of new extended crystal defects. The growth rate achieved under these conditions was approximately 0.05 mm/h. The nitrogen donor concentration in the grown 3C-SiC crystals was determined to be equal to (2-6)×1018 cm-3. © 2007 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2007.nat.dphy.IAP.LAP.growth
Keywords: A2. Bulk growth; A2. Modified Lely method; A2. Physical vapor transport; B1. 3C-SiC

Growth of diamond on silicon during the bias pretreatment in chemically vapour deposition of polycristalline diamond films - Ristein, Jürgen; Hundhausen, Martin; Ley, Lothar; et al. (Journal of Applied Physics, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.growth

Growth of high-quality homoepitaxial diamond films by HF-CVD - Stammler, Markus; Eisenbeiß, Henrick; Ristein, Jürgen; Neubauer, Jürgen; Göbbels, Matthias; Ley, Lothar; Ristein, Jürgen; Ley, Lothar (Diamond and Related Materials, 2002)
Defined growth of high-quality crystalline diamond films is necessary for manufacturing of electronic devices. Several groups have already worked on this topic and the main challenges remaining are the suppression of crystalline defects, the reduction of impurities and higher growth rates. High-quality homoepitaxial diamond films were produced in a hot filament chemical vapor deposition (HF-CVD) system with and without addition of nitrogen to the gas phase. Substrates were (100)-oriented synthetic Ib diamonds (Sumitomo) with a maximum misorientation angle of 0.3° as determined by X-ray diffraction. By adjusting the α parameter independently to a value close to two using polycrystalline diamond films on silicon growth rates of up to 500 nm/h could be achieved while simultaneously keeping the density of unepitaxial crystallites below 10 cm-2. The surface roughness (RMS) was below 1 nm in a 1 × 1-μm2 area. Impurities were studied by photoluminescence and cathodoluminescence spectroscopy. For the films deposited without intentional nitrogen addition, nitrogen-related impurities could only be detected by low temperature photoluminescence indicating a very low concentration. At 1.68 eV we observed the signature of the Si-vacancy complex probably caused by evaporation of Si from the tungsten filament. © 2002 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2002.nat.dgeo.IGM.LM.growth
Keywords: Diamond growth and characterization; HF-CVD; Homoepitaxy; Luminescene

Herstellung und Charakterisierung stickstoffreicher, qualitativ hochwertiger homo-epitaktischer Diamantfilme mittels Heißdraht-CVD - Eisenbeiß, Henrick; Stammler, Markus; Ristein, Jürgen; Ley, Lothar; Göbbels, Matthias; Neubauer, Jürgen (European Journal of Mineralogy, 2001)
UnivIS-Import:2015-03-09:Pub.2001.nat.dgeo.IGM.LM.herste

High field transport in the inversion layer of amorphous silicon thin film transistors - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1996)
The temperature and field dependence of the channel conductivity of a short-channel amorphous silicon thin film transistor were measured. The data are analyzed in the framework of the effective temperature model in which it is assumed that the transport properties depend only on an effective temperature that is calculated from the electric field and temperature. It is found that this model has to be refined in order to take into account the energy dependence of the localization length of the conduction band tail states and the field dependence of the dimensionless factor entering the formula for the effective temperature.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.highfi

High resolution surface sensitive C1s core level spectra of clean and hydrogen terminated diamond (100) and (111) surfaces - Maier, Florian; Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B - Condensed Matter and Materials Physics, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.IAP.exphys.highre

High Sensitivity photoelectron yield spectroscopy with computer-calculated electron optics - Ristein, Jürgen; Ley, Lothar; et al. (Review of Scientific Instruments, 1993)
An improved spectrometer design for photoelectron yield spectroscopy is described. Basis of the new spectrometer is a computer-designed electron optics that images the emission spot into the electron multiplier and thereby improves the sensitivity for electrons emitted from the sample. The collection efficiency was experimentally determined to 98.3%. A background of stray electrons which limits the ultimate sensitivity of the method could be substantially reduced by minimizing multiple beam reflections and by coating critical surfaces with a high work function material such as platinum. As a result, photoyield spectra of Au with a dynamical range of ten orders of magnitude are routinely obtained.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.highse

Hydrogenation of 6H-SiC as a Surface Passivation Stable in Air - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 2001)
We have terminated the hexagonal (0001) and (0001̄) surfaces of 6H-SiC with a monolayer of hydrogen by exposing the SiC crystal to pure hydrogen at elevated temperatures. The surfaces exhibit sharp, background-free, and unreconstructed LEED patterns and the photoemission spectra show only bulk-related Si and C components and give no indication of additional unwanted absorbates. On the Si-terminated (0001) surface, a sharp doublet at 2130 cm -1 with a splitting of 6 cm -1 is observed in surface-sensitive infrared spectroscopy, which is due to monohydride Si-H stretching modes. The origin of the splitting is discussed. The hydrogenated surfaces are passivated chemically and electronically. The oxygen uptake is less than 2 at.% after 2 h air exposure without any sign of Si-O or C-O bond formation. The surface Fermi level is unpinned and exhibits its bulk position on n- and p-type samples. © 2001 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.hydrog
Keywords: Carbide (SiC); Chemical passivation; Electronic passivation; Hydrogen termination

Hydrogen bonding analysis in amorphous hydrogenated carbon by a combination of infrared absorption and thermal effusion experiments - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1996)
A detailed analysis of the bonding configurations of hydrogen in amorphous carbon has been performed by measuring infrared (IR) absorption spectra and mass separated thermal effusion transients on a series of a-C:H samples deposited under self bias potentials of the substrate electrode between 0 and -1000 V. The C-H stretching as well as the bending modes of the IR absorption spectra were analysed quantitatively using IR absorption cross-sections of organic molecules for the various vibrational modes. Thermal effusion from the same samples was monitored with a quadrupole mass analyser recording eighteen relevant masses between 1 and 44 amu simultaneously and comparing the observed fragmentation patterns quantitatively with those of H2, CH4, C2H4, C2H6, C3H6 and C3H8 as calibration gases.
UnivIS-Import:2015-04-14:Pub.1996.nat.dphy.IAP.exphys.hydrog

Hydrogen-terminated diamond electrodes: I. Charges, potentials, energies - Ristein, Jürgen; Zhang, Wenying; Ley, Lothar (Physical Review E, 2008)
Hydrogen-terminated intrinsic diamond is a most unusual insulator since in contact with air or electrolyte it develops a hole accumulation layer just below the surface. When immersed in electrolyte the hole concentration responds to ionic charges and potentials and this response can be monitored by measuring the conductance of the hole accumulation layer without interference form the bulk conductivity. This feature has been widely used for chemical sensors in the form of solution-gate field effect transistors (SGFET). Here we analyze the charge and the potential profiles in the diamond and the electrolyte, as well as the static differential capacitance of the diamond electrode under controlled potential conditions. From this analysis we derive expressions for the transfer characteristics of diamond-based SGFET's that faithfully describe experimental data presented here as well. This holds in particular for the threshold region of the transfer characteristics that can only be modeled if the unusual semiconducting properties of the diamond electrode are taken into account properly. From fits to our data we derive (among other things) a value of χ=-0.50±0.02 eV for the electron affinity of the hydrogen-terminated diamond surface in contact with aqueous electrolyte. © 2008 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.IAP.exphys.hydrog

Hydrogen-terminated diamond electrodes: II. Redox activity - Zhang, Wenying; Ristein, Jürgen; Ley, Lothar (Physical Review E, 2008)
One of the most attractive features of diamond is its robust p -type surface conductivity that develops spontaneously under atmospheric conditions on hydrogen-terminated samples. An electrochemical charge transfer between diamond and an air-borne redox couple has been suggested to be responsible for the spontaneous appearance of surface-near holes. We present direct proof for the redox activity of the diamond surface by measuring pH -dependent open circuit potentials and quasistatic polarization curves for hydrogen-terminated and partially oxidized diamond electrodes. Under open circuit conditions we find in fact a mixed (or corrosion) potential that is consistent with the simultaneous equilibriation of the electrode versus both the hydrogen-hydronium and the oxygen-hydroxyl redox couple. Our data show extremely long-time constants for establishing the redox equilibrium and very low exchange current densities making the identification and characterization of the redox process a demanding experimental task. © 2008 The American Physical Society.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.IAP.exphys.hydrog_1

Hydrogen termination and electron emission from CVD diamond surfaces: a combined SEM, PEEM, photoelectron yield, and field emission study - Ley, Lothar; Ristein, Jürgen; Stammler, Martin; et al. (Diamond and Related Materials, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.hydrog

Identification of carbon interstitials in electron irradiated 6H-SiC by use of a 13C enriched specimen - Ley, Lothar; Hundhausen, Martin; et al. (Physical Review B, 2002)
Samples of 6H-SiC have been electron-irradiated with electron energies in the range 100-300 keV in a transmission electron microscope. After irradiation the samples were transferred to microscopic low-temperature photoluminescence spectrometers and excited by 325-nm, 488-nm, and 514.5-nm lasers. Optical centers were observed that had high-energy local modes and, when samples that had been enriched with 13C during growth were examined, these local modes were split into triplets. The observations are interpreted as C-C dumb bells created from C interstitials generated during the irradiation process. This is the reported identification of self-interstitial atoms by photoluminescence in SiC.
UnivIS-Import:2015-04-14:Pub.2002.nat.dphy.IAP.LAP.identi

Implication of hydrogen-induced boron passivation in wet-chemically cleaned Si(111):H - Ristein, Jürgen; Ley, Lothar; et al. (Applied Surface Science, 1997)
Atomically-flat, hydrogen-terminated Si(111) surfaces with a boron concentration range of 4.5 ∼ 11 × 1018 cm-3 have been prepared by a standard RCA cleaning step and subsequent 40% NH4F immersion followed by pure water dipping. The surface Fermi level for as-prepared Si(111) lies near midgap as confirmed by X-ray or ultraviolet excited photoelectron spectroscopy (XPS/UPS) and Kelvin probe measurements although occupied gap states density as low as 1011 cm-2 at most is verified from an extremely low photoelectron yield for photons with energies below ∼ 5 eV. Annealing at 360°C for 5 min causes the Fermi level to shift towards the valence-band maximum top by ∼ 0.2 eV without an appreciable increase in the gap state density and a change in hydrogen surface termination. These observations imply a hydrogen-induced passivation of boron atoms in a surface layer during wet-chemical cleaning and the reactivation of such passivated boron atoms by 360°C annealing. For annealing temperatures above 460°C, hydrogen desorption from the surface results in a true pinning of the Fermi level close to midgap because of the generation of surface gap states.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.IAP.exphys.implic
Keywords: Hydrogen passivation; Kelvin probe; Photoelectron yield spectroscopy; Silicon; Valence band

Indentification of Dumb-Bell Shaped Interstitials in Electron Irradiated 6H-SiC by Photoluminescence Spectroscopy - Ley, Lothar; Hundhausen, Martin; et al. (Materials Science Forum, 2003)
UnivIS-Import:2015-04-14:Pub.2003.nat.dphy.IAP.LAP.indent

Individual electronic defect states in a-Si:H/a-SiNx double barrier structures - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1991)
Random telegraphic noise (RTN) in large area a-Si:H/a-SiNx:H double barrier structures (DBS) is due to the charging and discharging of individual trap states in the barrier layer. The effective device area is confined to a path of less than 10 μm diameter. This is verified through the local effect a focused laser beam has on the noise characteristics. The capture (τ-c) and emission (τ-e) time constants of the current controlling trap can be determined separately. Temperature and bias dependence of the time constants are discussed within a model of acceptor-like traps with strong electron-lattice coupling that are situated in the nitride barrier and exchange charge with the conduction electrons in the adjacent n+a-Si:H layers. © 1991 Elsevier Science Publishers B.V. All rights reserved.
UnivIS-Import:2015-03-05:Pub.1991.nat.dphy.IAP.exphys.indivi

Influence of ambient humidity on the surface conductivity of hydrogenated diamond - Mares, J. J.; Hubik, Pavel; Kristofik, Jozef; Ristein, Jürgen; Strobel, Paul; Ley, Lothar (Diamond and Related Materials, 2008)
The enhancement of the electrical conductivity of hydrogen-terminated diamond surfaces due to the adsorption of various chemical species represents a challenging problem and has a high application potential as well. In the transfer doping model of Maier et al. the presence of a water layer that forms spontaneously in moist atmospheres on any surface plays a crucial role. Hence, in the present contribution we have focused our attention on the influence of the relative humidity (RH) on the surface conductivity. In order to perform conductivity measurements in a wet atmosphere an original technique eliminating leakage effects due to adsorbed water was developed. The conductivity was measured at room temperature for RH between 2% and 100%. Despite a rather weak dependence on RH, three well distinguished regions can be identified in the conductivity as a function of RH. Not pretending to offer a first-principles account for this behaviour, a phenomenological explanation of the data is given. © 2008 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.IAP.exphys.influe
Keywords: Humidity; Hydrogenated diamond; Surface conductivity; Water monolayer

Influence of light on individual defect noise in a-Si:H/a-SiNx:H double barrier structures - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Applied Physics, 1994)
This paper investigates the effect of illumination on the trapping and detrapping properties of individual electronic defect states, by demonstrating this access to the microscopic mechanisms of capture and release of charge carriers at the site of a single trap. The stability of the environment of an individual defect is also probed using the noise behavior. It is concluded that individual defect noise in a-Si:H/a-SiNx:H double barrier structures is affected by low and medium intensity illumination, because of the changed occupation of the trap state responsible for random telegraph noise. High intensity illumination results in metastable modification of the individual defect configuration.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.IAP.exphys.influe

Influence of space charges on the resonant photoconductor employing a moving laser inducde grating - Hundhausen, Martin; Ley, Lothar; et al. (Applied Physics Letters, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.influe

Influence of substrate bias on the properties of a-C:H films prepared by plasma CVD - Hundhausen, Martin; Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
We have measured photoluminescence (PL) and Raman spectra for a series of amorphous carbon (a-C:H) films prepared in a RF-plasma CVD system. The negative bias voltage was varied between 0V and 950V. The samples seem to consist of two components. One polymeric component has a high band gap and gives strong luminesence above 2.1 eV with 0.6 eV band width. The second component shows the Raman spectrum that is typical for the sp2-clusters of hard carbon. We find that the hard carbon component seems to be absent for zero bias voltage. The PL for this sample, however, is strongest. We find a fatiguing of the luminescence during laser excitation. This fatiguing is weaker at 120 K, resulting in a higher PL-efficiency for this temperature. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.influe

Influence of the growth conditions of epitaxial graphene on the film topography and the electron transport properties - Weingart, S.; Bock, C.; Kunze, Ulrich; Emtsev, Konstantin; Seyller, Thomas; Ley, Lothar (Physica E-Low-Dimensional Systems & Nanostructures, 2010)
In this work we report on temperature-dependent magnetotransport measurements on epitaxial graphene grown on SiC(0 0 0 1) under different preparation conditions. We demonstrate that the temperature dependence of the charge carrier density and mobility is correlated to the annealing conditions during the graphitization process. As recently shown, SiC substrates annealed in an Ar atmosphere near atmospheric pressure exhibit continuous monolayer graphene films over 2 - 3 μ m wide and more than 50 μ m long terraces. For these films we determine a constant charge carrier density in the range from 1.4 K up to room temperature and an electron mobility exceeding 3000 cm (V s) at low temperatures. © 2009 Elsevier B.V. All rights reserved.
Keywords: Charge carrier density; Charge carrier mobility; Epitaxial graphene; Magnetotransport

Infrared spectroscopy of C-D vibrational modes on diamond (100) surfaces - Ley, Lothar; Ristein, Jürgen; et al. (Surface Science, 1999)
A high resolution analysis of C-D vibrational modes on single crystal diamond using Fourier transform infrared spectroscopy is reported. This method has the advantage over high resolution electron energy loss spectroscopy of a far superior resolution (< 1 cm-1 versus approx. 10 cm-1). The inherently low surface sensitivity of the former method was overcome by measuring the IR absorption in the attenuated total reflection mode employing a Ge prism. The use of deuterium instead of hydrogen avoids the interference from airborne hydrocarbon contamination. We present data on the diamond (100) surface that was deuterated in a microwave plasma and subjected to a series of isothermal annealing treatments at 700°C. The C-D stretching mode at 2181 cm-1) and the bending mode at 1054 cm-1 could be followed down to a tenth of a monolayer coverage. From the intensity ratio of these bands measured in s- and p-polarization the essentially perpendicular disposition of the C-D bonds has been inferred.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.infrar

Initial stages in the growth of polycrystalline diamond on silicon - Ristein, Jürgen; Hundhausen, Martin; Ley, Lothar; et al. (Diamond and Related Materials, 1993)
Polycrystalline diamond films prepared in a hot filament chemical vapour deposition reactor were investigated with Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) in order to identify chemically and structurally distinguishable phases during nucleation and early stages of diamond growth. This was achieved by investigating a series of films grown under identical conditions for 5 min to 4 h. In addition, the interface between a solid diamond film and its silicon substrate was studied after the film had been removed from the substrate. Carbon deposition commences initially with the simultaneous growth of diamond crystallites along scratches and a layer of microcrystalline graphite covering the remainder of the substrate. Small amounts of SiC could also be identified during the first 100 min of deposition. Once the individual diamond crystallites have grown together to form a continuous layer, the graphitic phase in the spectra is replaced by an amorphous carbon phase which we attribute to the grain boundaries between the crystals. Inspection of the film backside revealed that the amorphous carbon had merely overgrown the microcrystalline graphite which was still present as the major component. Only after prolonged growth times (24 h) did the Raman and XPS spectra exhibit the characteristic diamond features free from any other contributions. On the basis of these observations a model for the initial stages of diamond growth on Si is developed. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.initia

In-situ characterization of chemical annealing of a-Si:H by photoelectron spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
The effect of chemical annealing with atomic hydrogen on a-Si:H samples was investigated in situ using surface sensitive spectroscopies. Changes in the hydrogen concentration and configuration as well as in the near surface defect state density are observed and are compared to the corresponding changes with deposition temperature. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.insitu

Interface formation between hydrogen terminated Si (111) and amorphous hydrogenated carbon (a-C:H) - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Vacuum Science & Technology A, 1997)
In the last few years heterostructures consisting of a-C:H on top of crystalline silicon have revealed a number of interesting properties for electronic applications, for example, as a photodiode (see Ref. 1) or, very recently, as cold cathode electron emitter (see Ref. 2). For those applications the interface properties of the heterostructure play a key role. In this article the electronic and chemical nature of the interface between plasma deposited a-C:H in the form of diamondlike carbon (DLC) and hydrogen terminated silicon (111) was determined by in situ core level and valence band photoemission spectroscopy. The quantitative analysis of core level shifts and intensities indicate that both, an interface layer of mixed composition and a pure a-C:H layer, grow simultaneously with relative growth rates of 2:1 during the initial stages of the interface formation. The interface layer is first carbon rich and then approaches stoichiometric composition which is reached at an interface thickness of 18 Å. Then a reactive SiC interface is completed and acts as a diffusion barrier which prevents further extension of the interface region when the deposition of a-C:H proceeds. Aside from an acceptor passivation of the Si substrate, due to H atoms from the plasma, no overlayer induced band bending is measured. The valence band offset between Si and DLC is determined as 0.7±0.1 eV with the valence band edge of DLC below that of silicon. © 1997 American Vacuum Society.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.IAP.exphys.interf

Investigation of mass transport during PVT growth of SiC by 13C labeling of source material - Herro, Ziad Georges; Wellmann, Peter; Püsche, Roland; Hundhausen, Martin; Ley, Lothar; Maier, Matthias; Masri, P.; Winnacker, Albrecht (Journal of Crystal Growth, 2003)
We have investigated experimentally mass transport during physical vapor transport growth of silicon carbide (SiC). 13C was used as trace in order to determine mass transport paths inside the SiC source material as well as inside the gas room. The 13C concentration inside the SiC crystal, SiC source material and parts of the graphite growth cell was measured using micro-Raman spectroscopy and secondary ion mass spectroscopy. The SiC growth process was monitored using digital X-ray imaging. The presented method for the first time provides experimental access to mass transport which is of particular interest (i) for fundamental investigations, and (ii) for the verification of numerical modeling tools which are currently widely in use for the improvement of the SiC growth proces
Keywords: Growth from vapor; Mass transfer; Si13C

Investigation of mass transport during PVT growth of SiC by 13C labelling of source material - Hundhausen, Martin; Winnacker, Albrecht; Ley, Lothar; et al. (Journal of Crystal Growth, 2003)
We have investigated experimentally mass transport during physical vapor transport growth of silicon carbide (SiC). 13C was used as trace in order to determine mass transport paths inside the SiC source material as well as inside the gas room. The 13 C concentration inside the SiC crystal, SiC source material and parts of the graphite growth cell was measured using micro-Raman spectroscopy and secondary ion mass spectroscopy. The SiC growth process was monitored using digital X-ray imaging. The presented method for the first time provides experimental access to mass transport which is of particular interest (i) for fundamental investigations, and (ii) for the verification of numerical modeling tools which are currently widely in use for the improvement of the SiC growth process. © 2003 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.IAP.exphys.invest_6
Keywords: A1. Mass transfer; A2. Growth from vapor; B1. Si

Investigation of mass transport during SiC PVT growth using digital X-Ray Imaging, 13C labeling of source material and numerical modeling - Durst, Franz; Hundhausen, Martin; Winnacker, Albrecht; Ley, Lothar; et al. (Materials Science Forum, 2003)
We have analyzed the mass transport during physical vapor transport growth of SiC using 13C for labeling of the SiC gas species (i.e. Si 2C and SiC2) paths and digital x-ray imaging in order to monitor the evolution of the SiC crystal and SiC source material. The distribution of Si13C was investigated after growth by Micro-Raman spectroscopy. The slow onset of the 13C incorporation into the SiC crystal as well as the enrichment of 13C in the residual source material indicate that the major mass transport is conducted through the center of the source material and not along the hot crucible walls where SiC consumption is observed first. Numerical modeling of sublimation and recrystallization inside the SiC source material has been carried out. Effects like the formation of a condensed disk on top of the source material, consumption of SiC close to the hot crucible walls, etc. are described well. The experimental as well as numerical methods are believed to be useful tools for scaling up current growth setups towards large single crystal diameters.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.IAP.exphys.invest
Keywords: Physical Vapor Transport Growth; Raman Spectroscopy; Si; Source Material; X-Ray Imaging

Investigation of mass transport during SiCPVT growth using digital X-ray imaging, C-13 labeling of source material and numerical modeling - Wellmann, Peter; Herro, Ziad Georges; Selder, Markus; Durst, F.; Püsche, Roland; Hundhausen, Martin; Ley, Lothar; Winnacker, Albrecht (Materials Science Forum, 2003)
We have analyzed the mass transport during physical vapor transport growth of SiC using C-13 for labeling of the SiC gas species (i.e. Si2C and SiC2) paths and digital x-ray imaging in order to monitor the evolution of the SiC crystal and SiC source material. The distribution of (SiC)-C-13 was investigated after growth by Micro-Raman spectroscopy. The slow onset of the C-13 incorporation into the SiC crystal as well as the enrichment of C-13 in the residual source material indicate that the major mass transport is conducted through the center of the source material and not along the hot crucible walls where SiC consumption is observed first. Numerical modeling of sublimation and recrystallization inside the SiC source material has been carried out. Effects like the formation of a condensed disk on top of the source material, consumption of SiC close to the hot crucible walls, etc. are described well. The experimental as well as numerical methods are believed to be useful tools for scaling up current growth setups towards large single crystal diameter
Keywords: Physical Vapor Transport Growth; Raman Spectroscopy; Si13C; Source Material; X-Ray Imaging

Isotope-Disorder-Induced Line Broadening of Phonons in the Raman Spectra of SiC - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review Letters, 2001)
The linewidth of a phonon in isotopically disordered SiC was shown to be not depending on the degree of mass disorder but on the frequency of the phonons. The elastic scattering by mass fluctuations contributed to the linewidth and the scattering rate was proportional to the density of final phonon states.
UnivIS-Import:2015-04-14:Pub.2001.nat.dphy.IAP.LAP.isotop_54

Isotope Effects on the Raman Spectrum of SiC - Hundhausen, Martin; Ley, Lothar; et al. (Materials Science Forum, 2000)
Substituting 12C by the 13C isotope in SiC changes the Raman frequencies. We have used isotopic substitution in several polytypes of SiC (4H, 6H, 15R) to study the change in the phonon dispersion relation of SiC and compare the results with calculations based on a linear-chain model. In a second set of experiments we use isotopic substitution to study the incorporation of carbon from the crucible during the growth of SiC by the modified Lely technique. To this end, a stoichiometric mixture of silicon and pure 13C was used as the charge. The incorporation of 13C in the grown crystal as monitored by spatially resolved Raman spectroscopy yields a gradient of 13C that increases beginning at the seed crystal and reaches a maximum of approximately 40% within 300 μm; the equilibrium concentration of 13C is a mere 27% after 1.5 mm growth.
UnivIS-Import:2015-04-14:Pub.2000.nat.dphy.IAP.LAP.isotop

Is persistent photoconductivity in nipi-structures of amorphous silicon due to the Staebler Wronski e - Hundhausen, Martin; Ley, Lothar; et al. (Solid State Phenomena, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.IAP.exphys.ispers

Kinetics of field induced oxidation of hydrogen terminated Si(111) by means of a scanning force micoscope - Ley, Lothar; Hundhausen, Martin; et al. (Journal of Vacuum Science & Technology B: Microelectronics Processing and Phenomena, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.kineti

Kinetics of platinum silicide formation followed in situ by spectroscopic ellipsometry - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Vacuum Science & Technology A, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.kineti

Light-induced transient changes of the occupied density of defect states of a-Si:H - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1993)
We have investigated transient changes of the defect density of states upon laser illumination using Photoelectron Yield Spectroscopy. The spectra show an increase of the occupied defect density of states (ODOS) upon illumination between EF and EF-0.75 eV and a decrease in the region of deep tail states. The signal depends sub-linearly on the laser intensity and reaches ΔODOS ≈ 1017 cm-3 eV-1 at an intensity of 50 mW cm-2, the highest intensity used. Time resolved measurements reveal fast rise and slow decay times. We interpret the observed effect either as a signature of weak bond-dangling bond conversion or as an energy relaxation of defects. © 1993.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.lighti

Low-temperature ballistic transport in nanoscale epitaxial graphene cross junctions - Weingart, S.; Bock, C.; Kunze, Ulrich; Speck, Florian; Seyller, Thomas; Ley, Lothar (Applied Physics Letters, 2009)
We report on the observation of inertial-ballistic transport in nanoscale cross junctions fabricated from epitaxial graphene grown on SiC(0001). Ballistic transport is indicated by a negative bend resistance of R ≈-170 ω, which is measured in a nonlocal, four-terminal configuration at 4.2 and which vanishes as the temperature is increased above 80 K. © 2009 American Institute of Physics.

Low threshold electron emission from diamond - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1999)
We have studied the photoassisted electron emission of single-crystal diamond (111) for photon energies from just above the diamond band gap of 5.5 eV well into the sub-band-gap regime (hν≈2.8eV). As an independent parameter, the electron affinity was varied between -1.27 eV [negative electron affinity (NEA)] and +0.38 eV [positive electron affinity (PEA)] by changing the hydrogen coverage of the surface. A substantial sub-band-gap emission band with constant intensity is observed in all cases. Except for the NEA surfaces, it dominates the electron flux. We attribute this intense band to nanometer-size graphitic patches which cover less than 1% of the surface area. The low-energy threshold for this emission band is, however, not determined by intrinsic properties of graphite, but controlled by the work function of the surrounding diamond matrix. The details of this inhomogeneous emission model, which may have implications for the field emission from nanocrystalline diamond films, are discussed. ©1999 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.lowthr

Mechanism of reaktive Ion etching of 6H-SiC in CHF3/O2 gas mixtures - Ristein, Jürgen; Ley, Lothar; et al. (Materials Science Forum, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.IAP.exphys.mechan

Model for persistent photoconductivity in doping-modulated amorphous silicon superlattices - Hundhausen, Martin; Ley, Lothar (Physical Review B, 1985)
Doping superlattices prepared by depositing successively 105-AÌ-thick layers of n-type, intrinsic, and p-type amorphous hydrogenated silicon (n-i-p-i structures), exhibit persistent photoconductivity at room temperature. Persistent photoconductivity (PPC) is the excess dark conductivity that remains after the sample has been exposed to white, heat-filtered light and that decays on a time-scale of hours or days. We prove that PPC is a bulk effect and that the amount of light necessary to induce a certain level of PPC decreases exponentially with temperature. This temperature dependence corresponds to an activation energy of 1/40.4 eV for the creation of state PPC; a slightly higher activation energy (1/40.7 eV) for the quenching of PPC is deduced from the annealing behavior. Above around 400 K the sample can be transformed into a second metastable state C, which does not exhibit PPC. The fact that the generation of PPC is thermally activated is incompatible with an explanation of this effect simply in terms of metastable carriers which are spatially separated in the space-charge fields of the n-i-p-i structure. We propose instead that holes are trapped in acceptorlike centers, AX, in the p regions of the sample, whereas the balancing concentration of electrons, confined to the n layers by the n-i-p-i fields and thus prevented from recombining with the holes, are responsible for PPC. The AX centers possess, in analogy to the DX centers in Ga1-xAlxAs, a strong electron-lattice coupling which accounts for the thermal activation energies of hole capture and ionization. © 1985 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1985.nat.dphy.IAP.exphys.modelf

Modeling the evolution of ellipsometric data during the thermally induced Pt-silicide formation: activation energies and prefactors - Ley, Lothar; Hundhausen, Martin; et al. (Symposium. Materials Research Society, 1999)
The formation of Pt silicide (PtSi) by the thermally activated reaction of a 23 nm Pt layer on Si was monitored in situ by ellipsometry. Characteristic changes in the ellipsometric angles as a function of temperature signal the approach of two reaction fronts to the surface: one belonging to the Pt/Pt2Si and the other to the Pt2Si/PtSi interface. An analysis of the evolution of the ellipsometric angles as a function of temperature for different heating rates allows the accurate determination of the average activation energies of the two reactions. From a modeling of the optical data in terms of a specific reaction model further kinetic parameters such as the reaction rate constants and the actual distribution of activation energies have been deduced.
UnivIS-Import:2015-04-16:Pub.1999.nat.dphy.IAP.exphys.modeli

Molecular and electronic structure of PTCDA on bilayer graphene on SiC(0001) studied with scanning tunneling microscopy - Lauffer, Peter; Emtsev, Konstantin; Graupner, Ralf; Seyller, Thomas; Ley, Lothar (physica status solidi (b), 2008)
Epitaxial growth of graphene on SiC surfaces by solid state graphitization is a promising route for future development of graphene based electronics. In the present work we study the morphology and molecular scale structure of monolayer films of 3,4,9,10-perylene tetracarboxylic dianhydrid (PTCDA) on bilayer graphene on SiC(0001) by scanning tunneling microscopy (STM). First we discuss how the PTCDA molecules adsorb on bilayer graphene. We specially regard the density of PTCDA molecules at monolayer coverage. From the comparison with experiments on HOPG (Au(111) and Ag(110) from literature) we infer a non-planar adsorption geometry of PTCDA molecules on bilayer graphene. The electronic structure of the surrounding bilayer graphene substrate is investigated via scanning tunneling spectroscopy (STS) and reveals n-type doping of bilayer graphene during adsorption of PTCDA. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

MoO3 induces p-type surface conductivity by surface transfer doping in diamond - Xing, Kaijian; Xiang, Yang; Jiang, Ming; Creedon, Daniel L.; Akhgar, Golrokh; Yianni, Steve A.; Xiao, Haiyan; Ley, Lothar; Stacey, Alastair; McCallum, Jeffrey C.; Zhuiykov, Serge; Pakes, Christopher I.; et al. (Applied Surface Science, 2020)
Surface transfer doping of diamond using high electron affinity transition metal oxides (TMOs), such as MoO3, has emerged as a key enabling technology for the development of diamond-based surface two-dimensional (2D) electronics. However, the omission of a critical pre-annealing step in the device fabrication process to remove atmospheric adsorbates prior to TMO deposition, as seen in numerous studies, makes the role of TMOs ambiguous in light of air-induced surface conductivity, preventing a full understanding of the intrinsic surface transfer doping behavior of TMO-based surface acceptors. Here, using in-situ four-probe electrical measurements we explicitly show the insulating-to-conducting transition in diamond surface driven by MoO3 induced surface transfer doping. Variable-temperature Hall-effect measurements reveal weak temperature-dependence down to 250 mK, evidencing the 2D Fermi liquid nature of the resulting surface conducting channel on diamond. Using first-principles calculations, we confirm the interfacial charge exchange upon MoO3 adsorption leading to a degenerate hole conducting layer on diamond. This work provides significant insights into understanding the surface transfer doping of diamond induced by TMOs, and paves the way for the investigations of many interesting quantum transport properties in the resulting 2D hole conducting layer, such as phase-coherent magnetotransport, on diamond surface.
CRIS-Team Scopus Importer:2020-03-13
Keywords: 2DHG; Diamond; Molybdenum trioxide; Surface conductivity; Surface transfer doping

Moving Grating Technique: A New Method for the Determination of Electron and Hole Mobilities and their Lifetime - Hundhausen, Martin; Ley, Lothar; et al. (Applied Physics Letters, 1993)
A new technique to determine the mobilities and lifetime of photogenerated electrons and holes in semiconductors relies on the short circuit current that is induced perpendicularly to a moving interference grating. Theoretical expressions for the short circuit current are derived that relate the carrier mobilities and their lifetime to the velocity and spatial period of the grating. The technique has been implemented and was successfully applied to a-Si:H.
UnivIS-Import:2015-03-05:Pub.1993.nat.dphy.IAP.exphys.moving

Moving Photocarrier Grating Technique for Mobility and Lifetime Measurements in Amorphous Semiconductors - Hundhausen, Martin; Ley, Lothar; et al. (Materials Research Society Symposium - Proceedings, 1994)
In this paper we describe a new method for the determination of the carrier lifetime (τ) and the carrier mobilities (μn, μp) in semiconductors. This technique utilizes a moving intensity grating that is generated by superposition of frequency shifted laser beams for the illumination of the sample. The material parameters are extracted from the short circuit current in the sample induced by the moving grating as a function of it's velocity (υgr). We solve the continuity equations and Poisson's equation in the small signal approach for the modulated electron and hole densities and show how these densities result in an electric field that in turn acts on the electrons and holes in order to yield a short circuit current density jsc. Erom a fit of this expression for jsc to experimental data we determine μn, μp and T. © 1994 Materials Research Society.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.IAP.exphys.moving

Nanometerâscale modification of the tribological properties of Si(100) by scanning force microscope - Hundhausen, Martin; Ley, Lothar; et al. (Applied Physics Letters, 1995)
Hydrogenâterminated Si(100) surfaces were patterned on the nanometer scale using a conductingâprobe scanning force microscope (SFM) operating in air ambient. To generate the nanostructures, negative voltages were applied to the conductive SFM tip with respect to the sample while scanning in contact mode. After structuring, the same SFM tip was used to measure simultaneously the sample topography and the friction force between tip and sample. An increase in height by about three nanometers resulting from fieldâenhanced oxidation is observed in areas where the tip had been negatively biased with constant voltages above 7 V. The topographical change is accompanied by a relative increase of the friction force of about 20% over the structured areas. © 1995, American Institute of Physics. All rights reserved.
UnivIS-Import:2015-04-14:Pub.1995.nat.dphy.IAP.exphys.nanome
Keywords: ATOMIC FORCE MICROSCOPY; FRICTION; HYDROGENATION; NANOSTRUCTURES; OXIDATION; SILICON; STM; TOPOLOGY; TRIBOLOGY

Nanometer-scale field-induced oxidation if Si(111): H by a conducting-probe scanning force microscope: Doping dependence and kinetics - Hundhausen, Martin; Ley, Lothar; et al. (Applied Physics Letters, 1995)
Hydrogen-terminated Si(111) was patterned on the nanometer scale by field-induced oxidation using a biased conducting-probe scanning force microscope. The kinetics of oxide growth as well as its dependence on doping are investigated. Field-induced oxidation is observed for voltages exceeding a doping dependent threshold above which oxidation kinetics follows a power law.© 1995 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.1995.nat.dphy.IAP.exphys.nanome_5

Nanometer-scale modification of the tribological properties of Si(111):H surfaces performed and investigated by a conducting-probe scanning force microscope - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Vacuum Science & Technology B: Microelectronics Processing and Phenomena, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.nanome

New-surface dopant passivation after wet-chemical preparation of Si (111):H surfaces - Ley, Lothar; Ristein, Jürgen; et al. (Journal of Vacuum Science & Technology B, 1996)
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.newsur

Non contact temperature measurements of diamond by Raman spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Applied Physics, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.IAP.exphys.noncon

Nucleophilic-alkylation-reoxidation: A functionalization sequence for single-wall carbon nanotubes - Graupner, Ralf; Abraham, Jürgen; Wunderlich, David; Vencelová, Andrea; Lauffer, Peter; Röhrl, Jonas; Hundhausen, Martin; Ley, Lothar; Hirsch, Andreas (Journal of the American Chemical Society, 2006)
A new reaction sequence for the chemical functionalization of single-wall carbon nanotubes (SWNTs) consisting of the nucleophilic addition of t-BuLi to the sidewalls of the tubes and the subsequent reoxidation of the intermediates t-BuSWNT leading to t-BuSWNT was developed. During the formation of the t-BuSWNT, a homogeneous dispersion in benzene was formed due to the electrostatic repulsion of the negatively charged intermediates causing debundling. The entire reaction sequence can be repeated, and the degree of functionalization of the products (t-Bu)SWNT (m = 1-3) increases with increasing m. Degrees of functionalization expressed as the carbon-to-addend ratio of up to 31 were reached. The reaction was studied in detail by photoelectron spectroscopy, Raman spectroscopy, and scanning tunneling microscopy (STM). The C 1s core level spectra reveal that the nucleophilic attack of the t-BuLi leads to negatively charged SWNTs. Upon oxidation, this negative charge is removed. The valence band spectra of the functionalized samples exhibit a significant reduction in the π-derived density of states. In STM, the covalently bonded t-butyl groups attached to the sidewalls have been visualized. Raman spectroscopy reveals that addition of the nucleophile to metallic tubes is preferred over the addition to semiconducting tubes. © 2006 American Chemical Society.

Observation of folded-zone acoustical phonons by Raman scattering - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review B - Condensed Matter and Materials Physics, 1985)
UnivIS-Import:2015-03-05:Pub.1985.nat.dphy.IAP.exphys.observ

Ordered arrangement of 9-aminoanthracene on Au(1 1 1) surfaces: A scanning tunneling microscopy study - Lauffer, Peter; Graupner, Ralf; Jung, Adrian; Hirsch, Andreas; Ley, Lothar (Surface Science, 2007)
We present a scanning tunneling microscopy (STM) investigation of 9-aminoanthracene (AA) on the reconstructed Au(1 1 1) surface. The bare Au(1 1 1) surface shows the herringbone reconstruction which is conserved upon deposition of the organic molecules. Most of the AA molecules are found to decorate the regions of fcc-stacking of the gold surface where a periodic linear arrangement is observed. The orientation of the long molecule axis of individual molecules is along the 〈 0 1 over(1, ̄) 〉-directions of the Au substrate. In addition, for individual domains of the surface reconstruction, one of the three possible orientations is preferred. On substrate areas which exhibit a high step density, the steps are completely decorated by AA molecules. A detailed analysis of the STM images reveals that the molecules are located on top terrace levels. The fine structure of individual molecules on the terrace shows a clear dependence on the tunneling voltage and resembles the molecular orbitals of the free AA molecule. © 2007 Elsevier B.V. All rights reserved.

Origin of surface conductivity in diamond - Ristein, Jürgen; Maier, Florian; Ley, Lothar; et al. (Physical Review Letters, 2000)
Experimental evidence is presented which supports an electrochemical model for the pronounced surface conductivity of hydrogen-terminated diamond. In this model hydrogenation rises the valence band maximum (VBM) of diamond sufficiently with respect to the vacuum level to place it just above the chemical potential of electrons in the liquid phase (μe) of a mildly acidic water layer physisorbed at the surface. Electron transfer from diamond to the H3O+/(H2O + H2) redox couple accounts for the hole accumulation layer. In equilibrium, the diamond surface Fermi level position is pinned at μe which coincides essentially with the VBM. Small variations in that Fermi level position with respect to VBM and thus variations in conductivity with the pH value of the wetting layer and the H2 partial pressure are quantitatively accounted for via Nernst's equation.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.theori

Ozone-Mediated Polymerization of Fullerene and Fluorofullerene Thin Films - Strobel, Paul; Ristein, Jürgen; Ley, Lothar (Journal of Physical Chemistry C, 2010)
Films of an oxygen-linked fullerene polymer were synthesized by exposing about 15-nm-thick fullerite layers to ozone at room temperature. Moderate ozone exposure was found to lead to a polyoxifulleride that was stable in a vacuum up to at least 800 K. The oxidation and polymerization process was monitored by corelevel and valence-band photoelectron spectroscopy, which suggested that the bonding between fullerenes was by furan-like oxygen bridges and that the resulting polymer was three-dimensionally linked. The redox potential of the film was unaffected by this kind of polymerization, as witnessed by the unimpaired fullereneinduced surface conductivity of diamond. Hence, in addition to stabilization of the diamond surface conductivity, the polymerization is expected to be of considerable importance for C60-based bulk heterojunction organic solar cells, as well as for C60-based field-effect transistors. Similar albeit less effective thermal stabilization was also achieved for the fluorofullerene C60F48. © 2010 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.exphys.ozonem

Persistent Photoconductivity in Doping-modulated amorphous silicon superlattices - Hundhausen, Martin; Ley, Lothar (Journal of Non-Crystalline Solids, 1985)
Doping superlattices prepared by depositing successively 105 Å thick layers of n-type, intrinsic, and p-type amorphous hydrogenated silicon, respectively (nipi structures), exhibit persistent photoconductivity (PPC) at room temperature. We prove that PPC is a bulk effect and that its creation is thermally activated with an activation energy of ∼0.4 eV; a slightly higher activation energy (∼0.7 eV) is necessary for the quenching of PPC. The thermal activation of PPC is incompatible with an explanation of this effect simply in terms of metastable carriers which are spatially separated in the space charge fields of the nipi structure. We propose instead that holes are trapped in acceptor-like centers, AX, in the p-regions of the sample whereas the balancing concentration of electrons, confined to the n-layers by the nipi fields and thus prevented from recombining with the holes, are responsible for PPC. The AX centers possess, in analogy to the DX centers in Ga1-xAlxAs, a strong electron-lattice coupling which accounts for the thermal activation energies of hole capture and ionization. © 1985.
UnivIS-Import:2015-03-05:Pub.1985.nat.dphy.IAP.exphys.persis

Photoelectron spectroscopy of clean and hydrogen exposed diamond (111) surfaces - Ristein, Jürgen; Ley, Lothar; et al. (Surface Science, 1994)
The modifications of the (111) surfaces of a type-IIb natural diamond and a CVD diamond film upon annealing and exposure to atomic hydrogen have been examined by ultraviolet-excited (UPS) and X-ray excited (XPS) photoelectron spectroscopy. Besides the two surface configurations commonly described in the literature, i.e. the clean reconstructed surface and the one associated with a monohydride passivation, a third configuration which evolves upon extreme hydrogen exposure has been observed. © 1994.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.IAP.exphys.photoe

Photoelectron yield spectroscopy on negative electron affinity diamond surfaces: a contactless unipolar transport experiment - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 1998)
On the hydrogen-passivated negative electron affinity (100) and (111) surfaces of diamond no energy barrier prevents photoelectrons from exiting into the vacuum. Therefore, the photoelectron yield spectrum reflects volume rather than surface properties of the material, and the technique is in many aspects similar to photoconductivity experiments, albeit with the advantage of being selective to electrons exclusively (and not to holes). We have employed photoelectron yield spectroscopy to investigate deep defect states in natural and CVD diamond and to determine the electron diffusion length in type II b single crystals. For the latter aspect, the competition between electron and exciton transport plays an important role and the analysis of the yield spectra gives surprisingly large electron diffusion lengths of about 200 μm. © 1998 Elsevier Science S.A.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.IAP.exphys.photoe
Keywords: Diamond surface; Negative electron affinity; Photoelectron spectroscopy; Unipolar transport

Photoemission study of amorphous carbon modifications and comparison with calculated densities of states - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1996)
In this study we present photoemission data for three different types of amorphous carbon modifications (a-C:H, ia-C:H, and ta-C) that owe their properties to their different preparations by radio frequency plasma, plasma beam, or arc discharge. Their properties are investigated by means of their characteristic plasmon loss following the C 1s core level, the core-level shape itself, and by their valence bands. For all three amorphous modifications as well as for the two crystalline ones, diamond and graphite, we present density of states calculations which in the amorphous case are based on molecular-dynamics simulations. The electronic density of states is fitted to the data using photoemission cross sections and a model for the lifetime broadening. The agreement achieved is very good and confirms the validity of the predicted structures that do not possess any significant larger π clusters.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.photoe

Photoemission study of the silicate adlayer reconstruction on 6H-SiC(0001) - Ristein, Jürgen; Ley, Lothar; et al. (Materials Science Forum, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.photoe

Preparation and characterization of hydrogen terminated 6H-SiC - Ristein, Jürgen; Ley, Lothar; et al. (Materials Science Forum, 2001)
A hydrogen termination of the (0001) and (0001̄) 6H-SiC surfaces is achieved by a thermal treatment in ultra pure hydrogen. This results in unreconstructed and quasi-bulk terminated surfaces as demonstrated by a (1×1) LEED patterns which are stable in air. Photoelectron spectra show only bulk related Si 2p and C 1s lines and give no indication of any contamination. Using Fourier transform infrared spectroscopy (FTIR) in the attenuated total reflection (ATR) configuration Si-H stretching modes around 2130 cm-1 have been observed in p-polarization but not in s-polarization. This indicates that the Si-H bonds are oriented perpendicular to the surface. Electronically, hydrogenation leads to a complete passivation of the surface with no pinning of the Fermi level. After annealing at 800°C in UHV the hydrogen completely desorbs and the surface periodicity changes from (1×1) to (√3×√3)R30°. The photoemission spectra of this (√3×√3)R30° structure are characteristic for a surface with Si adatoms in T4 configuration which is formed via a disproportionation of SiC at the surface.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.prepar

Purification of Single‐Walled Carbon Nanotubes Studied by STM and STS - Vencelová, Andrea; Graupner, Ralf; Ley, Lothar; Abraham, Jürgen; Holzinger, Michael; Whelan, Paul; Hirsch, Andreas; Hennrich, Frank; Kappes, Manfred (Molecular Nanostructures, 2003)

Quantitative determination of oxidative defects on single walled carbon nanotubes - Jung, Adrian; Graupner, Ralf; Ley, Lothar; Hirsch, Andreas (physica status solidi (b), 2006)
A large variety of functional groups (i.e. carboxyl, carbonyl, aldehyde, alcohol) - representing the different oxidation states of carbon - can be produced by oxidative treatment of single walled carbon nanotubes (SWCNTs), depending on duration and temperature of the process. For subsequent functionalization steps it is essential to know the quantitative amount of the functional groups being converted in a chemical reaction. X-Ray Photoelectron Spectroscopy (XPS) proved to be a useful tool for such determination. Here, the asymmetry of the C1s core level in SWCNTs and the unknown peak positions of the functional groups prevented a detailed analysis of the produced oxidized carbon species. In this work we present an effective method to overcome this problem using XPS correlated with ab-initio calculations of the Mulliken charges in functionalized SWCNTs. © 2006 WILEY-VCH Verlag GmbH & Co. KGaA.

Quantitative evaluation of biaxial strain in epitaxial 3 C- SiC layers on Si(100) substrates by Raman spectroscopy - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Applied Physics, 2002)
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.IAP.exphys.quanti

Quasi-freestanding Graphene on SiC(0001) - Speck, Florian; Ostler, Markus; Röhrl, Jonas; Jobst, Johannes; Waldmann, Daniel; Hundhausen, Martin; Ley, Lothar; Weber, Heiko B.; Seyller, Thomas (Materials Science Forum, 2010)
We report on a comprehensive study of the properties of quasi-freestanding monolayer and bilayer graphene produced by conversion of the (6√3×6√3)R30° reconstruction into graphene via intercalation of hydrogen. The conversion is confirmed by photoelectron spectroscopy and Raman spectroscopy. By using infrared absorption spectroscopy we show that the underlying SiC(0001) surface is terminated by hydrogen in the form of Si-H bonds. Using Hall effect measurements we have determined the carrier concentration and type as well as the mobility which lies well above 1000 cm2/Vs despite a significant amount of short range scatterers detected by Raman spectroscopy. © (2010) Trans Tech Publications.
UnivIS-Import:2015-04-14:Pub.2010.nat.dphy.IAP.LAP.quasif
Keywords: ARPES; Graphene; Hydrogen; Infrared absorption spectroscopy; Intercalation; Raman spectroscopy; XPS

Raman excitation profiles of 3C-, 4H-, 6H-, 15R- and 21R-SiC - Hundhausen, Martin; Ley, Lothar; et al. (Materials Science Forum, 2003)
The excitation energy dependence of the Raman scattering intensities of longitudinal modes of various SiC-polytypes was measured in the UV-spectral range for excitation energies tuned between 3.8eV and 5eV. The Raman scattering intensity of the unfolded longitudinal optical mode shows a pronounced decrease for all polytypes in the UV-spectral range, except for 3C-SiC. It is shown, that the position of the decrease in the intensity is related with the bandgap of the polytype under consideration. We explain this decreasing scattering intensity by a destructive interference of a resonant and an non-resonant contribution to the Raman scattering cross-section.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.IAP.exphys.ramane
Keywords: Excitation Profiles; Hexagonality; Polytypes; Raman Spectroscopy

Raman scttering in polycrystalline 3C-SiC: influence of stacking faults - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review B, 1998)
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.IAP.exphys.ramans

Raman spectra of epitaxial graphene on SiC(0001) - Röhrl, Jonas; Hundhausen, Martin; Emtsev, Konstantin; Seyller, Thomas; Graupner, Ralf; Ley, Lothar (Applied Physics Letters, 2008)
We present Raman spectra of epitaxial graphene layers grown on 63×63 reconstructed silicon carbide surfaces during annealing at elevated temperature. In contrast to exfoliated graphene a significant phonon hardening is observed. We ascribe that phonon hardening to a minor part to the known electron transfer from the substrate to the epitaxial layer, and mainly to mechanical strain that builds up when the sample is cooled down after annealing. Due to the larger thermal expansion coefficient of silicon carbide compared to the in-plane expansion coefficient of graphite this strain is compressive at room temperature. © 2008 American Institute of Physics.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.IAP.exphys.ramans

Random telegraphic noise in large area a-Si:H/a:Si1􀀀xNx double barrier structures - Ley, Lothar; Hundhausen, Martin; et al. (Journal of Non-Crystalline Solids, 1989)
Random telegraphic noise (RTN) with an amplitude of about 1% has been observed in the current through a-Si:H/a-Si1-xNx:H double barrier structures. The area of the devices, 0.25 mm2, is five orders of magnitude larger than the area of the devices where RTN has previously been observed. The power spectra of the noise can be fitted by a superposition of Lorentzians from which average switching times are deduced. The switching times are thermally activated with activation energies between 0.2 and 0.6 eV and they depend on bias voltage. Assuming that the current through these structures is confined to microchannels of cross section area < 1μm2 the RTN and its characteristics are explained by the random charging and discharging of individual traps placed in the vicinity of the current channel.
UnivIS-Import:2015-03-05:Pub.1989.nat.dphy.IAP.exphys.random

Recovery of surface conductivity of H-terminated diamond after thermal annealing in vacuum - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 2004)
A unique feature of diamond among other semiconductors is the formation of a high conductive p-type layer which is usually obtained after hydrogen-termination of the surface. It is generally accepted that the appearance of surface conductivity (SC) requires the presence of atmospheric adsorbates. We present a combination of conductivity and spectroscopic measurements dealing with the loss and the formation of SC as a function of annealing in vacuum (temperatures 60-900°C) and exposure to different atmospheres. For temperatures below 190°C in vacuum the SC decreases by more than five orders of magnitude and comes back to its initial value when the sample is exposed to air. After annealing between 250 and 700°C exposure to normal atmospheric conditions is no longer sufficient to recover SC, although the H termination is preserved. In this state the SC is fully restored upon air exposure after the surface has been exposed to ozone or oxygen radicals. We propose a model where oxygen-related sites are catalytically involved in the transfer-doping mechanism such that the rate of electron transfer from the diamond into solvated adsorbates is enhanced.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.IAP.exphys.recove

Resonant photoconductor structures for the generation of microwave currents: Importance of space charges - Hundhausen, Martin; Ley, Lothar; et al. (proc. 23rd Int. Conf. on the Physics of Semiconductors, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.IAP.exphys.resona

Sensitive measurement of laser induced photocarrier gratings in semiconductors by optical heterodyne detection - Hundhausen, Martin; Ley, Lothar; et al. (proc. 23rd Int. Conf. on the Physics of Semiconductors, 1996)
UnivIS-Import:2015-04-16:Pub.1996.nat.dphy.IAP.exphys.sensit

Signature of the weak bond-dangling bond conversion process in a-Si:H as seen by total photoelectron yield spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (MRS Proceedings, 1993)
Photoelectron Yield Spectroscopy is one of the most direct methods to study the density of gap states of amorphous semiconductors. We have made use of it to investigate the transient changes of the density of gap states of a-Si:H upon illumination with above-band-gap light. An excitation density of 50 mW/cm2 of 532 nm light from a frequency doubled Nd-YAG laser was modulated with frequencies between 0.1 Hz and 10 KHz and the transient response of the photoelectron yield signal was monitored by gated electron counting or a lock-in amplifier. From this we deduce a reversible increase of the occupied density of defect states under illumination with a maximum Δg to approximately 1017 cm-3 eV-1 at about 0.3 eV below the Fermi energy and a decrease below EF-0.75 eV, i.e. in the region of deep tail states. The effect exhibits a wide spectrum of time constants involved. Based on additional transient surface photo voltage measurements as well as numerical simulations we argue that the observed redistribution of states is not due to a light induced change in surface band bending or due to a mere excitation of electrons from occupied to empty states. Instead, we interpret the observed effect as a conversion of weak to dangling bonds, i.e. a precursor of the Staebler-Wronski Effect, lacking however the final step of hydrogen stabilization necessary for the creation of metastable defects.
UnivIS-Import:2015-04-16:Pub.1993.nat.dphy.IAP.exphys.signat

Spectroscopic Investigations of Diamond/Hydrogen/Metal and Diamond/Metal Interfaces - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 2001)
The formation of metal contacts on diamond surfaces is of decisive importance for the material's application in semiconductor devices. We present an investigation of the barrier heights of metals on diamond (111) single crystal surfaces by a combination of spectroscopic and structural methods. Two metals with different work functions and chemical reactivities, aluminium and gold were chosen as model systems for Schottky and ohmic contacts, respectively. Particular attention was paid to the role hydrogen termination of diamond has for the metal film morphology and the barrier heights. To this end diamond/metal contacts on hydrogenated and dehydrogenated diamond were investigated. Core-level spectroscopy was used to monitor chemical reactions between diamond and metal, metal-induced band bending, and the barrier heights. The morphology of the evaporated metal films was investigated by low energy electron diffraction (LEED), atomic force microscopy (AFM), and secondary electron microscopy (SEM). © 2001 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.spectr
Keywords: Hydrogen; Metal-diamond interface; Schottky/ohmic contacts

Steady-state hopping conduction in the conduction band tail of a-Si:H studied in thin - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review B - Condensed Matter and Materials Physics, 1995)
UnivIS-Import:2015-03-05:Pub.1995.nat.dphy.IAP.exphys.steady

Strong spin-orbit interaction induced by transition metal oxides at the surface of hydrogen-terminated diamond - Xing, Kaijian; Creedon, Daniel L.; Yianni, Steve A.; Akhgar, Golrokh; Zhang, Lei; Ley, Lothar; McCallum, Jeffrey C.; Qi, Dong Chen; Pakes, Christopher I. (Carbon, 2020)
Hydrogen-terminated diamond possesses an intriguing p-type surface conductivity which is induced via thermodynamically driven electron transfer from the diamond surface into surface acceptors such as atmospheric adsorbates, a process called surface transfer doping. High electron affinity transition metal oxides (TMOs) including MoO3 and V2O5 have been shown to be highly effective solid-state surface acceptors for diamond, giving rise to a sub-surface two-dimensional (2D) hole layer with metallic conduction. In this work, low temperature magnetotransport is used as a tool to show the presence of a Rashba-type spin-orbit interaction with a high spin-orbit coupling of 19.9 meV for MoO3 doping and 22.9 meV for V2O5 doping, respectively, through the observation of a transition in the phase-coherent backscattering transport from weak localization to weak antilocalization at low temperature. Surface transfer doping of diamond with TMOs provides a 2D hole system with spin-orbit coupling that is over two times larger than that reported for diamond surfaces with atmospheric acceptors, opening up possibilities to study and engineer spin transport in a carbon material system.
CRIS-Team Scopus Importer:2020-04-24

Structure and electronic states of ultrathin SiO2 thermally grown on Si(100) and Si(111) surfaces - Ley, Lothar; Ristein, Jürgen; et al. (Applied Surface Science, 1997)
The chemical and electronic structures of ultrathin SiO2 thermally grown on Si(100) and Si(111) have been investigated by using Fourier-transform infrared attenuated total reflection (FT-IR-ATR) and X-ray or ultraviolet excited photoelectron spectroscopy (XPS/UPS), respectively. A red-shift of the p-polarized LO phonon peak observed for oxides thinner than 2 nm indicates that compressively strained Si-O-Si bonds exist near the SiO2/Si interface. The extent of the structural strain induced in the interface region is found to be smaller for SiO2 grown at 1000°C on Si(100) than 1000°C SiO2 on Si(111) or 800°C SiO2 on Si(100). It is also found that, from the onset of the energy loss signal for Ols photoelectrons, the bandgap of the oxides thicker than ∼ 2.3 nm is 8.95 ± 0.05 eV irrespective of the oxide thickness. For oxides thinner than ∼ 2.3 nm, a remarkable increase in the 5-9 eV energy loss signal for O1s photoelectrons is observed. This could be attributed to not only the contribution of suboxides at the interface but also the built-in stress in the interface region which causes the band edge tailing.
UnivIS-Import:2015-03-05:Pub.1997.nat.dphy.IAP.exphys.struct

Structure of interfaces in a-Si:H/a-SiNx:H superlattices - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Applied Physics, 1991)
UnivIS-Import:2015-03-05:Pub.1991.nat.dphy.IAP.exphys.struct

Study of the temperature induced polytype conversion in cubic SiC by Raman spectroscopy - Hundhausen, Martin; Ley, Lothar; et al. (Materials Science Forum, 2004)
Using 3C-SiC crystals grown on undulant Si(100) substrates as seed crystals, bulk growth of 3C-SiC by the modified Lely method has been demonstrated. However, particularly at elevated growth temperatures, macroscopic 6H-SiC inclusions can be observed in the grown crystals. Here we investigate the temperature dependence of the 3C- to 6H-SiC transformation of the CVD substrate by Micro Raman Spectroscopy after annealing at temperatures between 1700°C and 2100°C. At temperatures above 1800°C 3C- to 6H-SiC polytype transformation is observed that proceeds from the top side of the crystals. However, the conversion appears to be stopped at domain boundaries that are oriented along 111 planes.
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.IAP.LAP.studyo
Keywords: Annealing CVD; Cubic SiC; Raman spectroscopy

Surface band bending and electron affinity as a function of hole accumulation density in surface conducting diamond - Edmonds, M. T.; Pakes, C. I.; Mammadov, Samir; Zhang, Wenying; Tadich, A.; Ristein, Jürgen; Ley, Lothar (Applied Physics Letters, 2011)
Simultaneous measurements of work function (φ) and C 1s core level shift were employed to determine the change in electron affinity (X) and band bending as a function of hole sheet density on H-terminated diamond for atmospheric and fullerene (C60 F48) induced surface conductivity. Contrary to earlier investigations, it is shown that changes in work function do not reflect variations in the position of the surface Fermi level in response to surface transfer doping. Instead, with a transition from -0.96 to -0.33 eV, X accounts for a significant amount of the change in φ for hole densities between 5× 108 and 4× 1013 cm-2. © 2011 American Institute of Physics.
UnivIS-Import:2015-03-09:Pub.2011.nat.dphy.IAP.exphys.surfac

Surface band bending and surface conductivity of hydrogenated diamond - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 2003)
We establish a strict correlation between the total photoelectron yield spectra and the surface conductivity of hydrogenated diamond. The decomposition of the yield spectra into electron and exciton derived contributions requires an upward surface band bending to accompany surface conductivity, while an essentially flat band or downward band bending is observed after removing the surface conductivity by annealing in vacuum. Between the two competing models proposed for surface conductivity with a sheet hole density of 10 13 cm -2, these results favor the surface transfer-doping model strongly over the subsurface acceptor model.
UnivIS-Import:2015-03-09:Pub.2003.nat.dphy.IAP.exphys.surfac

Surface conductivity induced by fullerenes on diamond: passivation and thermal stability - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 2006)
The surface conductivity of hydrogen terminated diamond under atmospheric conditions is a well known phenomenon. Inspired by the surface transfer doping model [F. Maier, M. Riedel, B. Mantel, J. Ristein, L. Ley, Phys. Rev. Lett. 85, (2000) 3472] we have recently investigated thin C60 layers as an alternative to atmospheric adsorbates. We could indeed show that C60 induces a sub-surface accumulation layer that results in a surface conductivity comparable to the air induced one [P. Strobel, M. Riedel, J. Ristein, L. Ley, Nature 430, (2004) 439]. In the present work we investigate fluorinated fullerenes, namely C60F18, C60F36, and C60F48, as transfer dopants. The surface conductivity induced by fluorinated fullerenes increases with higher fluorination and achieves for C60F48 a level that exceeds that observed under atmospheric conditions by up to a factor of three. Furthermore, we study the thermal stability of the fullerene layers on diamond and their stabilisation by passivation with different dielectric films (SiO, CaF2, and Si3N4). In the case of fluorinated fullerenes we observe a significant improvement in thermal stability after passivation with dielectrics but the pristine conductivity level cannot be kept. A different kind of stabilisation is achieved for C60. After the simultaneous exposure to oxygen, light, and temperature of about 150 °C the surface conductivity induced by C60 is stable up to 350 °C in vacuum with an undiminished doping efficiency. We ascribe this effect to an oxygen mediated polymerisation of the C60 layer. © 2005 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.IAP.exphys.surfac_6
Keywords: Fullerenes; p-type doping; Passivation; Thermal stability

Surface conductivity of diamond: a novel doping mechanism - Ristein, Jürgen; Strobel, Paul; Ley, Lothar (Advances in Science and Technology, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.IAP.exphys.surfac_8

Surface conductivity of diamond: a novel transfer doping mechanism - Ristein, Jürgen; Ley, Lothar; et al. (Physica B-Condensed Matter, 2006)
A novel doping mechanism is presented for the case of diamond that does not rely on the incorporation of dopant atoms into the crystal lattice as in conventional doping. Instead, adsorbates provide the acceptor level into which electrons are transferred, leading to a two-dimensional subsurface hole accumulation layer with an areal concentration of up to 10 13 cm -2. Two acceptor systems are discussed. One is based on the charge exchange between diamond and solvated H + ions in a water layer that forms spontaneously on all surfaces in air. The other relies on the high electron affinity of fullerenes and fluorinated fullerenes that act as efficient acceptors when physisorbed at the surface. In either case, the extremely low ionization energy of hydrogen terminated diamond that is matched by no other semiconductor is a necessary requirement for transfer doping. © 2006 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.nat.dphy.IAP.exphys.surfac_7
Keywords: Devices; Diamond; Doping; Surfaces

Surface Conductivity of Diamond as a Function of Nitrogen Doping - Ristein, Jürgen; Ley, Lothar; et al. (physica status solidi (a), 2001)
The surface conductivity of diamond has recently attracted a lot of interest since a number of electronic applications proposed for diamond are based on this effect. Nevertheless, its microscopic origin is still a matter of debate. We describe in the following experiments in which the impact of the balk defect concentration of diamond on the surface conductivity is investigated. The experiments show that surface conductivity is suppressed in the presence of donor-like nitrogen defects although the surfaces are clearly hydrogen (or deuterium) terminated. We suggest compensation of the surface or surface near acceptors to be the reason for this suppression. A quantitative discussion shows that the doping capability of the surface acceptors is exhausted at lateral concentrations of about 3 × 1013 cm-2.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.surfac

Surface conductivity of nitrogen-doped diamond - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 2002)
Synthetic type Ib diamond crystals with (001) surfaces that expose growth sectors of different nitrogen content have been used to study the phenomenon of p-type surface conductivity upon plasma hydrogenation and upon overgrowth with thin epitaxial CVD diamond layers. We found that an unbiased microwave-driven hydrogen plasma leads to surface conductivity only on well-defined regions on the substrates that correlate with growth sectors of low nitrogen content; whereas no conductive layer is found on top of growth sectors with higher nitrogen concentrations in the range of 200 ppm. After growing a homoepitaxial intrinsic diamond layer of only 20 nm on top of the nitrogen doped diamond, these differences are no longer observed and surface conductivity is established homogeneously over the whole sample. The same effect can be achieved by exposing the Ib substrates to a pure hydrogen plasma provided the sample is biased with an additional DC voltage of -250 V. Both results can be understood in the framework of the surface transfer doping model suggested earlier by Maier and colleagues when the compensation of nitrogen donors by surface acceptors and their passivation by hydrogen is taken into account. The quantitative discussion shows that the doping capability of the surface acceptors is exhausted at lateral concentrations of approximately 1×1013 cm-2, which also corresponds to the maximum hole concentration usually observed in hydrogen-induced p-type conductive layers. © 2002 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.IAP.exphys.surfac
Keywords: Diamond defects; Electronic states; Impurities; Surface

Surface doping: a special feature of diamond - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Physics: Condensed Matter, 2001)
A unique feature of diamond surfaces is a highly conductive p-type layer, which is usually observed when the surfaces are hydrogen terminated. This phenomenon has recently attracted a lot of interest since a number of electronic applications proposed for diamond are based on the effect. Nevertheless, its microscopic origin is still a matter of debate. In this paper we propose an electron transfer from the diamond valence band to adsorbates at the surface to be the effective doping mechanism. These adsorbates act not as isolated species but as components of a mildly acidic aqueous surface layer and thus charge exchange has to be described by electrochemical arguments. The model is supported by experiments, which show that the hydrogenation of the surface is necessary but not sufficient for inducing the hole accumulation layer at the surface.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.surfac_8

Surface electronic properties of diamond - Ristein, Jürgen; Maier, Florian; Ley, Lothar; et al. (physica status solidi (a), 2000)
The influence of surface states, defects and adsorbates on the electronic properties of diamond surfaces are discussed. As far as surface states and reconstructions are concerned the principal crystallographic surfaces, (100), (111) and (110), are essentially understood in their adsorbate free form and also when terminated by hydrogen. The role of surface defects is addressed and the correlation between the position of the surface Fermi level and the concentration of surface defects is discussed quantitatively for p-type diamond. Hydrogen passivation leads to a negative electron affinity of diamond surfaces due to a dipole layer which is induced by the heteropolar carbon-hydrogen bonds of the surface atoms. This aspect is discussed quantitatively. Finally, an experiment in which photoelectron spectroscopy and in situ conductivity measurements were combined to elucidate the surface conductivity of diamond is described and analyzed.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.surfac

Surface Fermi level position of hydrogen passivated Si (111) surfaces - Ristein, Jürgen; Ley, Lothar; et al. (Applied Physics Letters, 1996)
Core and valence band photoemission data of hydrogen passivated Si(111):H surfaces yield surface Fermi level positions that are indicative of a near-surface depletion layer for n- as well as p-type samples. The bulk Fermi level positions are attained after annealing at ∼400°C. These observations are explained in terms of a hydrogen induced passivation of donors and acceptors in a surface layer of the order of a μm as a result of the wet-chemical etching procedure. © 1996 American Institute of Physics.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.surfac

Surface sensitive K-edge absorption spectroscopy of clean and hydrogen terminated diamond (111) and (100) surfaces - Ristein, Jürgen; Ley, Lothar; et al. (Physical Review B, 1999)
We present a detailed electron yield spectroscopy study of the pre-K-edge features of single-crystal diamond (100) and (111) surfaces which are induced by optical transitions from the C 1s core level into excited states. Both hydrogen-terminated and hydrogen-free surfaces were investigated. A sharp maximum at ℏω =287.2 eV in the spectra of the (111) and (100) surfaces is characteristic of the monohydrogenated surfaces, which is interpreted as a strongly localized intramolecular excitation within the C-H bond of a surface atom. The clean diamond surfaces show maxima in the absorption spectra at ℏω=284.6 eV for the (111) surface, and at 284.15 and 286.3 eV for the (100) surface which are interpreted as surface core excitons. From the polarization dependence of the intensities of these features and by using dipole selection rules, the point-group symmetry of the excited states involved in the optical transition is deduced. The transition energies of the absorption maxima of the clean surface are discussed in terms of pertinent band-structure calculations and excitonic effects. ©1999 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.surfac

Surface state dispersions on diamond (100) and (111) surfaces - Ristein, Jürgen; Ley, Lothar; et al. (the Physics of Semiconductors, 1996)
UnivIS-Import:2015-04-20:Pub.1996.nat.dphy.IAP.exphys.surfac_7

Surface transfer doping of diamond - Ristein, Jürgen; Ley, Lothar; et al. (Nature, 2004)
The electronic properties of many materials can be controlled by introducing appropriate impurities into the bulk crystal lattice in a process known as doping. In this way, diamond (a well-known insulator) can be transformed into a semiconductor, and recent progress in thin-film diamond synthesis has sparked interest in the potential applications of semiconducting diamond. However, the high dopant activation energies (in excess of 0.36 eV) and the limitation of donor incorporation to (111) growth facets only have hampered the development of diamond-based devices. Here we report a doping mechanism for diamond, using a method that does not require the introduction of foreign atoms into the diamond lattice. Instead, C60 molecules are evaporated onto the hydrogen-terminated diamond surface, where they induce a sub-surface hole accumulation and a significant rise in two-dimensional conductivity. Our observations bear a resemblance to the so-called surface conductivity of diamond seen when hydrogenated diamond surfaces are exposed to air, and support an electrochemical model in which the reduction of hydrated protons in an aqueous surface layer gives rise to a hole accumulation layer. We expect that transfer doping by C60 will open a broad vista of possible semiconductor applications for diamond.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.IAP.exphys.surfac

Surface transfer doping of diamond by fullerene - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 2005)
Fifteen years after Landstrass and Ravi [1] [I.M. Landstrass, K.V. Ravi, App. Phys. Lett, 55 (1989) 975] reported a hydrogen induced surface conductivity of diamond, it has now been established that the phenomenon is based on a sub-surface hole accumulation layer. A quantitative model for the origin of this layer has been proposed by our group earlier and is based on the charge exchange between the diamond surface and solvated ions in a water layer that forms spontaneously on all surfaces in air. The process relies on the particularly low ionization energy of the hydrogenated diamond surface [2] [F. Maier, M. Riedel, B. Mantel, J. Ristein, and L. Ley, Phys. Rev. Lett. 85 (2000) 3472]. Here, we report on fullerenes (C60) and fluorinated fullerenes (C60F48) as alternative adsorbate systems. They induce surface conductivity on a level comparable (C60) or even higher (C60F48) than that observed under atmospheric conditions. Whereas in the case of C60 efficient doping requires the formation of the van-der Waals solid on top of the surface of diamond, C60F 48 acts as surface acceptor even as isolated molecule. In both cases, the doping efficiency can be modeled by considering the electrochemical equilibrium between the diamond and the adsorbate layer. © 2005 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.nat.dphy.IAP.exphys.surfac
Keywords: Diamond film; p-type doping; Surface electronic properties

Temperature induced polytype conversion in cubic silicon carbide studied by Raman spectroscopy - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Applied Physics, 2004)
In this paper, we study the polytype transformation of cubic silicon carbide (3C-SiC) by micro Raman spectroscopy. Two sets of samples are investigated. First, physical vapor transport (PVT) grown samples, grown on chemical vapor deposition (CVD) substrates at growth temperatures between 1800 and 1950°C. The microscopic images of the cross sections and the Raman spectra taken on these grown crystals show a growing fraction of 6H-SiC inclusions with increasing growth temperature. To decide whether these polytype inclusions are induced by the PVT growth process or by the temperature treatment of the CVD substrates, we studied the temperature induced polytype coversion of cubic CVD substrates grown on undulant Si(100) surfaces which were used as seed crystals for the PVT growth. The CVD substrates were annealed in the temperature range between 1700 and 2100°C. The results of this annealing series are similar to the results we find in the PVT grown samples. Therefore we argue that the polytype conversion is not induced by the PVT growth process but a result of the heat treatment of the CVD seed crystals. © 2004 American Institute of Physics.
UnivIS-Import:2015-04-14:Pub.2004.nat.dphy.IAP.LAP.temper

The correlation between surface conductivity and adsorbate coverage on diamond as studied by infrared spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 2001)
A high-resolution analysis of C-H vibrational modes on a single crystal diamond(100) surface using Fourier-transform infrared (FTIR) spectroscopy in combination with conductivity measurements is reported. On a plasma-hydrogenated diamond(100) surface, the IR spectra measured in the multiple internal reflection mode reveal three absorption lines. Two of them at 2921 and 2854 cm-1 vanish in air at an annealing temperature of 190°C and are assigned to the antisymmetric and symmetric CH2 stretching modes of a physisorbed hydrocarbon species, respectively. The third band at 2897 cm-1 has a width of 16 cm-1, is stable up to 230°C and is associated with the stretching frequency of C2H2 monohydride units on the C(100) 2 × 1:2H surface. Upon annealing in air at temperatures lower than 200°C, the surface conductivity is reversibly reduced by up to five orders of magnitude. After cooling down to room temperature, it recovers the value of 1 × 10-5 Ω-1 measured immediately after the plasma hydrogenation with a time constant of several days. Annealing at 230°C destroys the surface conductivity irreversibly and yields conductance values below the measurement limit of 5 × 10-12 Ω-1. We show that the chemisorbed hydrogen in the C2H2 configuration, together with at least one physisorbed species, is responsible for the surface conductivity of hydrogen-terminated diamond(100). © 2001 Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.thecor
Keywords: Diamond surfaces; Hydrogen bonding; IR spectroscopy; Surface conductivity

The density of states of ta-C, ta-C:H and a-C:H as determined by x-ray excited photoelectron spectroscopy and molecular dynamics calculation - Ristein, Jürgen; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1996)
The valence band spectra of amorphous carbon modifications with and without hydrogen covering the range from so-called diamond-like carbon to mainly tetrahedrally coordinated (ta-C, ta-C:H) carbon were determined by photoelectron spectroscopy. The results are compared with densities of states calculated for finite clusters with structures that were obtained from molecular dynamics calculations. From this comparison correlations between spectroscopic features and structural elements in the amorphous carbon modifications are derived.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.theden

The Effect of Addend Variation on the Solubility of Single-Wall Carbon Nanotubes - Abraham, Jürgen; Hirsch, Andreas; Hennrich, Frank; Kappes, Manfred; Dziakova, Andrea; Graupner, Ralf; Ley, Lothar (Structural and Electronic Prpoperties of Molecular Nanostructures, 2002)

The formation and stability of sub-micron clusters in silane and argon plasmas - Hundhausen, Martin; Ley, Lothar (Journal of Non-Crystalline Solids, 1991)
We have studied the formation of small silicon clusters in the plasma of a capacitively coupled RF-glow discharge deposition system used for the preparation of a-Si:H. These particles were detected by light scattering and are found to grow from SiH4 in the gas phase only if the temperature during deposition is substantially lower than in plasmas normally used for the deposition of device-quality films. We find that the particles are confined to the inner plasma region. This is explained by the fact that the particles become negatively charged due to the higher mobility of electrons vs. the positive ions. On account of their charge the particles are confined to the positive plasma region. The influence of the negative charge on the defect density of the a-Si:H forming the small particles is discussed. © 1991 Elsevier Science Publishers B.V. All rights reserved.
UnivIS-Import:2015-03-05:Pub.1991.nat.dphy.IAP.exphys.thefor

The hydrogenated and bare diamond (110) surface: a combined LEED-, XPS-, and ARPES study - Hammer, Lutz; Ristein, Jürgen; Ley, Lothar; et al. (Surface Science, 1999)
The atomic and electronic structures of the hydrogenated and hydrogen-free diamond (110) surface are investigated by low-energy electron diffraction (LEED), angle-resolved photoelectron spectroscopy (ARPES), and X-ray induced core-level spectroscopy (XPS). From the C 1s core-level spectra, different states of surface termination can be distinguished. The plasma-hydrogenated surface exhibits a surface C 1s component shifted by 0.8 eV towards a higher binding energy, which we attribute to coadsorbed hydrocarbons. During thermal annealing up to 900 °C, gradual desorption first of the hydrocarbons and then of hydrogen yields a clean surface with a surface C 1s component shifted by -1.1 eV and an increase in downward band bending of about 1.2 eV compared to the as-prepared surface. From the valence band spectra, we conclude that an essentially hydrogen-terminated surface is maintained at an annealing temperature of 600-800 °C. All states of the surface are unreconstructed. After the plasma treatment, the surface reveals monoatomic steps running parallel to the [11̄0] direction. From an analysis of the extinction of LEED reflexes, we conclude that within the chains of surface atoms running along [11̄0], the C-C bond length is uniformly altered in a way that keeps the chains undimerized. Finally, for the hydrogen-free surface, an occupied surface band is observed with a dispersion of 0.35 eV between Γ̄ and J̄ that lies entirely below the valence band maximum.
UnivIS-Import:2015-03-05:Pub.1999.nat.dphy.IAP.exphys.thehyd

The Impact of Ozone on the Surface Conductivity of Single Crystal Diamond - Ristein, Jürgen; Ley, Lothar; et al. (Diamond and Related Materials, 2004)
The electron affinity and thereby the ionisation energy of single crystal diamond (100) is changed between -1.3 and +1.7 eV and 4.2 and 7.2 eV, respectively, by stepwise oxidation of hydrogenated surfaces in ozone-rich atmospheres. Simultaneous measurements of the surface conductivity (SC) demonstrate that even for slight oxidation the SC disappears in air whereas SC is fully maintained in an ozone-rich atmosphere up to a partial oxygen coverage of ∼40%. These results constitute the first observation of electron transfer to the O3/O2 + OH- redox couple that extends on account of its lower electrochemical potential (compared to the H3O+/H2 couple active in normal air) the SC to samples with electron affinities higher than that of the hydrogenated surface. Thereby, the results confirm the basic tenet of the electrochemical transfer doping model in which the ionisation energy of diamond and the electrochemical potential of aqueous redox couples govern the charge exchange that leads to SC by a subcutaneous hole accumulation layer. In a second set of experiments, it is shown that for samples annealed in vacuum at temperatures between 250 and 700 °C SC is lost and does not recover upon air exposure despite an intact hydrogen coverage of the surface. However, after a brief exposure to ozone that does not result in any measurable oxidation, SC is recovered upon exposure to air. Explanations of this effect in terms of ozone-induced catalytic centers or passivation of donor-like surface defects are being offered. The relevance of these results for similar observations in connection with UV illumination is being alluded to. © 2003 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dphy.IAP.exphys.theimp
Keywords: Diamond properties and applications; Hydrogen terminated; Ozone; Surface conductivity

The influence of chemical annealing on the electronic properties of amorphous silicon - Ristein, Jürgen; Ley, Lothar; et al. (Solid State Phenomena, 1995)
UnivIS-Import:2015-04-16:Pub.1995.nat.dphy.IAP.exphys.theinf

The influence of diamond chemical vapour deposition coating parameters on the micro structure and properties of titanium substrates - Heinrich, Georg; Grögler, Thomas; Rosiwal, Stefan; Singer, Robert; Stöckel, R.; Ley, Lothar (Diamond and Related Materials, 1996)
In contrast to their excellent mechanical properties, titanium alloys possess poor wear characteristics. Diamond coatings appear to be a promising solution for the wear problem. Using standard deposition parameters for silicon (diamond scratched surface; microwave chemical vapour deposition, 500 W, 800°C for 4 h, 50 mbar with an atmosphere of 1% CH4+99% H2) good coatings on pure titanium were obtained. The mechanical properties of the titanium are strongly influenced by the processing temperature and the gas atmosphere. As a result of the hydrogen adsorption, grain coarsening and formation of titanium hydride occur and subsequently the low cycle fatigue strength decreases by an order of magnitude. However, by annealing in vacuum (800°C for 2 h, furnace cooled) the hydrogen can be removed again and the initial mechanical properties can almost completely be restored. Based on scanning electron microscopy micrographs, Auger analysis, X-ray diffraction and microhardness measurements a basic understanding of the microstructural changes was developed. The surface structure may be visualized as consisting of five zones, created during the deposition process (diamond layer/nucleation zone/reaction layer/gradient layer/affected substrate).
Keywords: Dehydrogenation; Mechanical properties; Microstructure; Titanium

The influence of surface treatment on the electronic structure of CVD diamond films - Ristein, Jürgen; Hundhausen, Martin; Ley, Lothar; et al. (Diamond and Related Materials, 1994)
The electronic structure of CVD diamond surfaces has been studied by core level and valence band photoelectron spectroscopy. Upon annealing at 870 °C, a band of surface states appears within the top 6 eV of the valence bands which is accompanied by a decrease in spectral intensity around 9 eV and a band bending of 0.4 eV. Similar changes could be induced by Ar ion bombardment. Exposure to atomic hydrogen largely restored the original spectra. These observations are compared with corresponding data on single-crystalline diamond surfaces. Similarities and differences are discussed in terms of structural models of the CVD diamond surface. © 1994.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.IAP.exphys.theinf

The Purification of Single-Walled Carbon Nanotubes studied by X-ray induced Photoelectron Spectroscopy - Graupner, Ralf; Vencelová, Andrea; Ley, Lothar; Abraham, Jürgen; Hirsch, Andreas; Hennrich, Frank; Kappes, Manfred (Molecular Nanostructures, 2003)

The role of adsorbates and defects on diamond surfaces - Ristein, Jürgen; Ley, Lothar; et al. (New Diamond and Frontier Carbon Technology, 2000)
The influence of surface termination, defects, and adsorbates on the electronic properties of diamond surfaces is discussed. Hydrogen passivation leads to a negative electron affinity of diamond surfaces due to a dipole layer which is induced by the heteropolar carbon-hydrogen bonds of the surface atoms. This aspect is discussed quantitatively. Next, the role of surface defects is addressed and the correlation between the position of the surface Fermi level and the concentration of surface defects is discussed for p-type diamond. Finally, experiments combining total photoelectron yield spectroscopy and in situ conductivity measurements are reported which elucidate the phenomenon of surface conductivity of hydrogenated diamond. An electrochemical model is proposed to explain this unique feature of diamond surfaces.
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.therol_6
Keywords: Adsorbates; Diamond surface; Electronic properties

The role of hydrogen for field emission from chemical vapour deposited diamond and nanocrystaline diamond powder - Ley, Lothar; Ristein, Jürgen; Stammler, Martin; et al. (Journal of Applied Physics, 2000)
UnivIS-Import:2015-03-09:Pub.2000.nat.dphy.IAP.exphys.therol

Ti-Silicide Formation During Isochronal Annealing Followed by in situ Ellipsometry - Hundhausen, Martin; Ley, Lothar; et al. (Microelectronic Engineering, 2001)
Single-wavelength ellipsometry is employed to monitor in situ the reaction of titanium layers of different thickness (10-80 nm) with Si(100) to form titanium silicides during heating at constant rates up to 100 K/min. Previous studies performed on the platinum/silicon system showed that by the use of `Kissinger' plots the activation energy for the formation of the intermediate silicide phase Pt 2Si and that of the final PtSi can be determined with an accuracy of 50 meV. Additionally, by directly modelling the evolution of the ellipsometric data as they were obtained during the temperature ramp the pre-exponential growth factor of the two reactions was determined as well. In the present study the reaction of Ti with Si to the intermediate C49-TiSi 2 phase was followed and the activation energy of this reaction was determined to be 2.30 eV. The isomorphous C49-/C54-TiSi 2 phase transition can also be traced by ellipsometry. However, the change in the ellipsometric angles is less pronounced which might be ascribed to a TiO x overlayer. Complementary to the ellipsometric analysis of the silicidation, the chemical composition of the reaction products and the thicknesses of the formed layers were identified at crucial stages of the reaction by X-ray diffraction, Raman spectroscopy, and Rutherford backscattering spectroscopy.
UnivIS-Import:2015-03-09:Pub.2001.nat.dphy.IAP.exphys.tisili

Towards wafer-size graphene layers by atmospheric pressure graphitization of silicon carbide - Emtsev, Konstantin; Bostwick, A.; Horn, Karsten; Jobst, Johannes; Kellogg, Gary L.; Ley, Lothar; McChesney, J.; Ohta, T.; Reshanov, Sergey; Röhrl, Jonas; Rotenberg, E.; Schmid, A.; et al. (Nature Materials, 2009)
Graphene, a single monolayer of graphite, has recently attracted considerable interest owing to its novel magneto-transport properties, high carrier mobility and ballistic transport up to room temperature. It has the potential for technological applications as a successor of silicon in the post Moore's law era, as a single-molecule gas sensor, in spintronics, in quantum computing or as a terahertz oscillator. For such applications, uniform ordered growth of graphene on an insulating substrate is necessary. The growth of graphene on insulating silicon carbide (SiC) surfaces by high-temperature annealing in vacuum was previously proposed to open a route for large-scale production of graphene-based devices. However, vacuum decomposition of SiC yields graphene layers with small grains (30-200 nm; refs 14-16). Here, we show that the ex situ graphitization of Si-terminated SiC(0001) in an argon atmosphere of about 1 bar produces monolayer graphene films with much larger domain sizes than previously attainable. Raman spectroscopy and Hall measurements confirm the improved quality of the films thus obtained. High electronic mobilities were found, which reach =2,000 cm 2 V 1 s 1 at T=27 K. The new growth process introduced here establishes a method for the synthesis of graphene films on a technologically viable basis.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.IAP.LAP.towwar

Universal Work Function of Metal Oxides Exposed to Air - Rietwyk, Kevin J.; Keller, David A.; Ginsburg, Adam; Barad, Hannah Noa; Priel, Maayan; Majhi, Koushik; Yan, Zhi; Tirosh, Shay; Anderson, Assaf Y.; Ley, Lothar; Zaban, Arie (Advanced Materials Interfaces, 2019)
Metal oxides are the cornerstone of thin-film electronics, a multibillion dollar industry, because they possess a wide variety of optoelectronic properties, exhibit novel functionalities, and can typically be fabricated from cheap, nontoxic raw materials. However, for thin-film electronics to achieve further market penetration, it is necessary to replace expensive vacuum-based fabrication processes with low-cost, large-scale solution-based methods. Here, the influence of exposure to air on the band energies of metal oxides is investigated, which is crucial for predicting the operation of thin-film devices under realistic conditions. A universal reduction in the work function is observed across 18 oxides, and for a subset, n-type doping of the surfaces is observed after they have been exposed to atmosphere for extended periods of time. These effects arise from charge transfer events with the ubiquitous water layer that forms on surfaces in air. A quantitative analysis of the changes is provided based on the electrochemical transfer doping model, and the amount of transferred charge and the equilibrium work function of oxides in air are calculated which are in agreement with the measurements.
CRIS-Team Scopus Importer:2019-05-17
Keywords: air; band alignment; electrochemical transfer doping; metal oxides; work function

Valence band and gap state spectroscopy of amorphous carbon by photoelectron emission techniques - Ristein, Jürgen; Ley, Lothar; et al. (Amorphous Carbon:State of the Art, 1998)
UnivIS-Import:2015-04-16:Pub.1998.nat.dphy.IAP.exphys.valenc